Molecular analysis of time-dependent DNA and RNA degradation in bloodstains: differential stability of HBA and ALAS2 gene targets and its forensic implications - Rahat Bukhari; Rahat Abdul Rehman; Midhat Salman; Allah Rakha; Anam Munawar; Shahid Nazir; Muhammad Farhan Khan; Zunaira Batool (Molecular Biology Reports, 2026)

Neuroprotective effect of Continentalic acid by targeting NF-κB/Bcl-2 and oxidative stress signaling in traumatic brain injury in male BALB/c mice - Sana Zafar; Maryam Jamil; Muhammad Ibrar Khan; Ashraf Ullah Khan; Kifayat Ullah Shah; Eun Kyoung Seo; Salman Khan (Molecular Biology Reports, 2026)

Transformation-driven reorganization of cross-domain microbial interactomes reflects multifunctionality loss in alpine wetlands - Awais Iqbal; Muhammad Maqsood Ur Rehman; Abraham Allan Degen; Salman Khan; Zhanhuan Shang (Soil Ecology Letters, 2026)

Zircon and apatite geochemical and isotopic constraints on magma fertility and magmatic evolution of porphyry CuAu mineralization at the Ting Darigun prospect, Chagai Belt, Western Pakistan - Muhammad Hafeez; Xiaoyong Yang; Ahmed Shah; Zahra Abbasi; Salman Ahmed Khattak; Ibrar Khan (Lithos, 2026)

A 25-year analysis of intracerebral hemorrhage mortality trends among patients with essential hypertension: Insights from the CDC WONDER database (1999–2024) - Mohammad Hamza Bin Abdul Malik; Muhammad Arham; Muhammad Awais Bin Abdul Malik; Allah dad; Anfal Hamza; Ayesha Ihsan; Tahira Nazir; Faseeh Haider; Ali Haq; Muhammad Salman Sabri (Next Research, 2026)

European sorghum from field to functional food: Nutritional composition, bioactive compounds, and processing-induced biotransformation - Jakub Frankowski; Mateusz Labudda; Muhammad Salman Farid; Anna Przybylska-Balcerek; Katarzyna Szambelan; Maciej Ireneusz Kluz; Przemysław Łukasz Kowalczewski; Miroslava Kačániová; Łukasz Łopusiewicz (Food Bioscience, 2026)

Iron chelation therapy and splenomegaly severity in transfusion dependent beta thalassemia major: assessment of ferritin patterns and clinical outcomes - Sidra Jamil; Narendar Kumar; Shaib Muhammad; Reham Bakhsh; Azfar Athar Ishaqui; Tauqeer Hussain Mallhi; Khalid Orayj; Salman Ahmed; Amar Hussain (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Optimization of energy transition pathways in the lime industry: A superstructure approach - Rafailia Mitraki; Muhammad Salman; Daniel Flórez-Orrego; François Maréchal; Grégoire Léonard (Journal of Cleaner Production, 2026)

Food, culture, and biodiversity: An ethnogastronomic assessment of wild plants among different ethnic communities in Azerbaijan - Sayyara Ibadullayeva; Farah Amrahova; Muhammad Zafar; Salman Majeed; Nahaa M. Alotaibi; Khuzin Dinislam; Muhammad Rizwan Khan; Jushkinbek Yuldoshev; Islom Khudayberganov; Adnan Amin (International Journal of Gastronomy and Food Science, 2026)

Urban heat island effect in China: Multidimensional insights into urbanization’s impact - Yusen Luo; Wei Xu; Muhammad Salman; Chao Wu (Environment, Development and Sustainability, 2026)

Palynological analysis of selected melliferous plant species in the Lesser Himalayas - Aroosa Habib; Muhammad Zafar; Iqra Qayyum; Salman Majeed; Saleh AlNadhari; Muhammad Rizwan Khan; Muhammad Ishtiaq Ali; Sayyara Ibadullayeva; Khuzin Dinislam; Shabir Ahmad (International Journal of Tropical Insect Science, 2026)

Retraction Note: Matrine alleviates neurobehavioral alterations via modulation of JNK-mediated caspase-3 and BDNF/VEGF signaling in a mouse model of burn injury - Adnan Khan; Bushra Shal; Muhammad Naveed; Bakht Nasir; Nadeem Irshad; Hussain Ali; Salman Khan (Psychopharmacology, 2026)

Hydrological Alterations and Soil Microbial Responses Under Prolonged Irrigation and Salinity Stress - Shakhobiddin Turdimetov; Mokhinur Musurmanova; Gulom Jurayev; Berdiyor Ixtiyor Ogli Omonboyev; Mohamed Fawzy Ramadan; Muhammad Ishtiaq Ali; Salman Majeed; Muhammad Rizwan Khan; Trobjon Makhkamov; Adnan Amin (Irrigation and Drainage, 2026)
The Mirzachol Oasis is one of the most important agroecological regions in Uzbekistan and has been subject to six decades of intensified irrigation, resulting in significant hydrological and soil changes. The impact on microbial communities below the surface is less well studied than its impact on the surface, but both affect soil health. This study addresses this gap by examining microbial communities, soil physicochemical parameters and historical irrigation data from 1960–2020 across six separate plots, including protected and irrigated plots. The results show that, due to organic matter accumulation and cultivation, extended irrigation increased microbial diversity and biogenicity in nonsaline soils (such as the U. Nasir and Yangi Hayot massifs). Nevertheless, secondary salinization disrupted nutrient cycling by suppressing functional microbial guilds, such as nitrifiers and cellulose‐degrading bacteria, in irrigated zones (e.g., the M. Uzoqov and Pakhtakor massifs). The salinization legacy reduces ecosystem stability, while older irrigated soils exhibit greater microbial resilience than recently irrigated or protected lands. Microbial activity was further influenced by seasonal variations, pH changes and groundwater fluctuations; salinity exacerbated reductions in fungal and actinomycete populations.

Retraction notice to “A step towards environmental mitigation: Do tourism, renewable energy and institutions really matter? A QARDL approach” [Sci. Total Environ. 778 (2021) 146209] - Zhan Zhan; Liaqat Ali; Salman Sarwat; Danish Iqbal Godil; Gheorghita Dinca; Muhammad Khalid Anser (Science of The Total Environment, 2026)

Chloride ions-assisted high-efficiency natural seawater splitting enabled by noble-metal-free MnOx(OH)y/GaN nanowires - Yumeng Li; Liang Qiu; Xiantong Zheng; Lin Yao; Muhammad Salman Nasir; Zijian Huang; Ying Li; Yixin Li; Ding Wang; Wenxing Yang; Jianyang Zang; Ping Wang; et al. (Science Bulletin, 2026)

Smart municipal waste management with source segregation and recovery optimization - Muhammad Waqas Iqbal; Jasim Alnahas; Shahbaz Khan; Muhammad Imran; Muhammad Salman Habib; Md Al-Amin Khan (Journal of Cleaner Production, 2026)

The cryoprotective blueprint of high-molecular-weight glutenin subunits: mechanisms linking genetics and structure to dough freezing tolerance – a review - Sameh Sharafeldin; Mahmoud Naser; Toheed Akbar; Samir Mowafy; Muhammad Salman Iqbal; Abeer M. Abd Elhamid; Muhammad Ahmad; Ghada M. Kholaf; Raghda A. Abu Ahmed; Zhao Liangxing; Luman Sang; Shen Qun (Food Chemistry, 2026)

Ethnobotany of desert medicinal plants and their sustainable ethnomedicinal utilization - Salman Majeed; Muhammad Zafar; Sayyara Ibadullayeva; Nahaa M Alotaibi; Sheikh Zain Ul Abidin; Muhammad Rizwan Khan; Sumreen Dawood; Khuzin Dinislam; Adnan Amin (The Science of Nature, 2026)

Pollen micromorphological variations in selected species of genus Ipomoea (Convolvulaceae) and their taxonomic significance - Aleena Gul; Muhammad Zafar; Salman Majeed; Muhammad Rizwan Khan; Samah A. Alharbi; Sayyara Ibadullayeva; Shomaila Ashfaq; Khuzin Dinislam; Adnan Amin; Samira Khudaverdiyeva (Plant Biosystems, 2026)

Multi-trait plant growth-promoting endophytic fusarium proliferatum from phoenix dactylifera enhanced wheat growth under drought stress condition - Salman Khan; Khalil Ur Rahman; Nida Karishma; Mamoona Rauf; Humaira Gul; Muhammad Hamayun; Abdulwahed Fahad Alrefaei; Faheem Anwar; Sajid Ali; Muhammad Arif (Acta Physiologiae Plantarum, 2026)

Evaluation of host suitability and larval instar effects on the reproductive potential of entomopathogenic nematodes against lepidopteran pests - Hina Safdar; Sumaira Maqsood; Salman Ghuffar; Aftab Ahmad; Muhammad Hafeez; Hifza Safdar; Tauseef Anwar; Huma Qureshi; Hossam S. El-Beltagi; Ibrokhim Ismoilov; Feruza Tukhtaboeva; Nazih Y. Rebouh; et al. (Crop Protection, 2026)

Multilevel barriers to antimicrobial stewardship in tertiary care hospitals: A comparative systematic scoping review of high-income versus low-/middle-income countries evidence mapped by study design and healthcare professionals - Azfar Athar Ishaqui; Zikria Saleem; Tauqeer Hussain Mallhi; Sultan M. Alshahrani; Khalid Orayj; Salman Ashfaq Ahmad; Rayah Asiri; Emad Ali Alsaleh; Muhammad Imran; Mohammed Ali Kaddoura; Bilal Jawed; Narendar Kumar; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Sustainable development of novel lime marble dust composite compressed earth blocks: mechanical and durability performance evaluation - Salman Farooq; Zia Ul Islam; Muhammad Isa Khan; Hamza Sajjad (Innovative Infrastructure Solutions, 2026)

Correction to: Diversity of wild Morchella (Ascomycota) revealed by integrated morphological and molecular analyses - Sania Shoukat; Nasir Mehmood; Salman Ghuffar; Sadiqa Bibi; Muhammad Rauf; Gulshan Irshad; Gule-e-Lalah Khan; Sumaira Maqsood; Tauseef Anwar; Huma Qureshi; Nazih Y. Rebouh; Salohiddinjon Yunusov; et al. (Folia Microbiologica, 2026)

Comparative analysis of volatile flavor compounds in lactic acid bacteria-bioacidified sour beer using HS-SPME/GC-MS and multivariate statistical methods - Wenxin Yang; Muhammad Salman Farid; Kaixin Cao; Yang He; Feiyu An; Yiming Liu; Cui Zhang; Rina Wu; Zhen Wu; Junrui Wu (Food Bioscience, 2026)

Liquid smoke characterisation and production from empty fruit bunches via consecutive pascalisation and microwave-assisted pyrolysis - Orchidea Rachmaniah; Wahyu Meka; Siti Nurkhamidah; Naomi Devina Surya Saputra; Muhammad Khasbi Ashshiddiqi; Tai Boon Tan; Chin Ping Tan; Mahardika Fahrudin Rois; Latifa Hanum Lalasari; Fernanda Maria Vanin; Salman Masoudi Soltani (Bioresource Technology Reports, 2026)

Plant viruses as next-generation vectors for transgene-free genome editing, gene regulation, and rapid crop improvement - Abdul Ali Azam; Muhammad Salman Iqbal; Huma Saleem; Revocatus Bahitwa; Hai Wang (Plant Molecular Biology, 2026)

A machine learning framework for evaluating cyclic resistance of sands with non-plastic fines - Arslan Mushtaq; Muhammad Salman; Muhammad Noman; Muhammad Faizan; Afaq Ahmed (Innovative Infrastructure Solutions, 2026)

Micromorphological and anatomical profiling of Vincetoxicum spirale (Apocynaceae): structural adaptations in a threatened riparian climber - Muhammad Rizwan Khan; Muhammad Zafar; Salman Majeed; Sayyara Ibadullayeva; Nigar Mursal; Nahaa M. Alotaibi; Muksin Khodjiev; Khuzin Dinislam; Enkelejda Kucaj (Plant Biosystems, 2026)

Trade adjusted carbon emissions and renewable energy electricity output: Evidence from method of moment quantile regression for N-11 economies - Maaz Amin; Salman Wahab; Bilal Ahmed; Muhammad Imran; Shahid Ali; Sakiru Adebola Solarin (Environment, Development and Sustainability, 2026)

Boundary-Consistent Ordinal Regression for wheat yield prediction using UAV-based multispectral time-series data - Muhammad Salman Akhtar; Zuhair Zafar; Zahid Mahmood; Muhammad Kashif Naeem; Kanat Yermekbayev; Muhammad Moazam Fraz (Computers and Electronics in Agriculture, 2026)

Open dumps as a critical source of per- and polyfluoroalkyl substances in agricultural soils of Pakistan: evidence of trifluoroacetic acid dominance - Amina Amanat; Mujtaba Baqar; Maosen Zhao; Faiqa Faryal; Mehmood Aslam; Muhammad Salman Mukhtar; Yiming Yao; Hongwen Sun (Environmental Pollution, 2026)

​​​​ Membrane active nanoemulgel incorporating Atorvastatin and carom seed essential oil for combating multidrug resistant microbes - Muhammad Ali; Niamat Ullah; Adnan Amin; Muhammad Zafar; Salman Majeed; Saleh AlNadhari; Sayyara Ibadullayeva; Nigar Murshal; Mukhayya Ruzieva; Islom. Khudayberganov; Khuzin Dinislam (Protoplasma, 2026)

Association of oral metoprolol exposure during heart failure hospitalization with death or readmission at 28-days and 6-months using a propensity score overlap-weighted EHR analysis - Azfar Athar Ishaqui; Emad Ali Alsaleh; Asaad Ahmed Asaad Khalil; Mohammed Ali Kaddoura; Khalid Orayj; Rayah Asiri; Sultan M. Alshahrani; Salman Ashfaq Ahmad; Narendar Kumar; Adnan Iqbal; Muhammad Bilal Maqsood (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Comparative disproportionality signals for methotrexate monotherapy versus methotrexate combined with hydroxychloroquine, leflunomide, or sulfasalazine in rheumatoid arthritis: newly highlighted signals evaluated using drug information safety profiles - Azfar Athar Ishaqui; Khalid Orayj; Zeeshan Ahmed; Salman Ashfaq Ahmad; Sultan M. Alshahrani; Rayah Asiri; Adnan Iqbal; Asaad Ahmed Asaad Khalil; Mohammed Ali Kaddoura; Muhammad Bilal Maqsood (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Comment on “Prescribing patterns of glucagon like peptide-1 receptor agonists in the Swedish capital region: a register-based cross-sectional study” - Muhammad Salman; Muhammad Hammad Chola; Muhammad Hasan (European Journal of Clinical Pharmacology, 2026)

A comprehensive review of thermal ablation technologies for transdermal drug delivery: mechanisms, commercial products, and future smart systems - Muhammad Murtaza; Salman Ali Khan; Hayat Khan; SK Safdar Hossain (Drug Delivery and Translational Research, 2026)

The first complete genome sequence of a highly pathogenic fowl adenovirus serotype 4 isolate from an infected chicken in Pakistan reveals the absence of a natural large genomic deletion - Salman Ahmad; Syeda Fakhra Waheed; Itra Ayoub; Ayesha Siddiqua; Soban Tufail; Sofia Irfan; Raheem Ullah; Muhammad Salahuddin Shah; Mazhar Iqbal; Moazur Rahman; Aamir Shehzad (Archives of Virology, 2026)

The impact of green brand image and green perceived risk on green trust and green purchase intention: the moderating role consumption values - Bilal Ahmed; Salman Wahab; Muhammad Imran; Muhammad Imran; Nawaz Ali Shah; Shamsher Ali (Environment, Development and Sustainability, 2026)

Designing glass materials for renewable-energy production through building integrated photovoltaics (BIPV) −A computational approach - Aqsa Aleem; Uzma Habib; Waqas Salman; Muhammad Tariq Saeed (Energy and Buildings, 2026)

Assessment of methane (CH4) and its nexus with meteorological variables using cross wavelet analysis over South Asia - Khadija Shakrullah; Salman Tariq; Muhammad Nasar-u-Minallah; Safdar Ali Shirazi; Kashif Mahmood (Theoretical and Applied Climatology, 2026)

Stem anatomical microcharacters and morphology as diagnostic botanical markers in Euphorbiaceae species - Sehrish Rubab; Salman Majeed; Sumreen Dawood; Muhammad Zafar; Modhi O. Alotaibi; Sayyara Ibadullayeva; Fakhra Bibi; Yusra Khan; Adnan Amin (The Science of Nature, 2026)

Micromorphological assessment of pollen and foliar epidermal traits in Solanaceae using SEM characterization - Mehral Azhar; Muhammad Zafar; Salman Majeed; Saleh AlNadhari; Sayyara Ibadullayeva; Muhammad Rizwan Khan; Khuzin Dinislam; Nigar Mursal; Amna Shahid; Enkelejda Kucaj (The Science of Nature, 2026)

Gastroprotective effect of Kahweol against ethanol-induced gastric ulcer by employing in silico, in vitro and in vivo approaches - Shahid Khan; Abdul Qadir; Jawad Azam; Muhammad Noman; Nadeem Ahmad; Zaheer Ul-Haq; Kashif Bashir; Tajamul Hussain; Salman Alrokayan; Muhammad Latif; Hussain Ali; Yousaf Kamal; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Anti-arthritic and anti-inflammatory potential of newly synthesized 2,3-disubsituted thiazolidine-4-one derivatives in CFA-induced arthritis model by targeting TLR4/NF-κB and MAPK signaling - Muhammad Ibrar Khan; Sana Zafar; Muzaffar Abbas; Ashraf Ullah Khan; Kifayat Ullah Shah; Salman Khan (Inflammopharmacology, 2026)

Integrated physicomechanical, petrographic, and geochemical evaluation of eocene carbonate aggregates from the Salt Range, Pakistan - Khawaja Shoaib Ahmed; Muhammad Basharat; Amir Shahzad; Yasir Sirfraz; Muhammad Tayyib Riaz; Usama Shabir Abbasi; Salman Rasheed (Innovative Infrastructure Solutions, 2026)

Trends in ADR reporting’ and the missing context: COVID-19, LMICs, and sociodemographic blind spots - Talha Ali; Muhammad Salman; Mateen Khan (European Journal of Clinical Pharmacology, 2026)

Optimization of Tissue Culture Media for Microtuber Development Incorporating Sugars and Zinc Nanoparticles - Muzammil Anwar Khan; Naima Huma Naveed; Aamir Ali; Muhammad Adeel; Aima Iram Batool; Tahir Shahzad; Muhammad Rizwan Khan; Salman Majeed (American Journal of Potato Research, 2026)

Diversity of wild Morchella (Ascomycota) revealed by integrated morphological and molecular analyses - Sania Shoukat; Nasir Mehmood; Salman Ghuffar; Sadiqa Bibi; Muhammad Rauf; Gulshan Irshad; Gule-e-Lalah Khan; Sumaira Maqsood; Tauseef Anwar; Huma Qureshi; Nazih Y. Rebouh; Salohiddinjon Yunusov; et al. (Folia Microbiologica, 2026)

The Atlantic salmon tongue mucosa functions as an active mucosal immune site capable of responding to a pathogen - Carlo C. Lazado; Elisabeth Ytteborg; Hanne Brenne; Muhammad Salman Malik; Malene Soleng; Erik Burgerhout; Aleksei Krasnov; Marianne Iversen (Fish & Shellfish Immunology, 2026)

Chitosan-mediated elicitation enhanced production of secondary metabolites and antioxidant assays in callus culture of Ocimum bacilicum L. (Purple Basil) - Gouhar Zaman; Samah Saleh Al-Shybany; Muhammad Naeem Bajwa; Muhammad Salman Khan; Muhammad Nadeem; Muhammad Zia; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Advancing Spatiotemporal Orthophoto Registration in UAV-based Crop Breeding Experiments Leveraging Field Geometric Features - Muhammad Salman Akhtar; Zuhair Zafar; Zahid Mahmood; Haris Khurshid; M. R. Naseem; Karsten Berns; Muhammad Moazam Fraz (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2026)

Genomic surveillance of Influenza, SARS-CoV-2, and RSV in patients from Islamabad and Rawalpindi, Pakistan: a 2023-24 perspective - Zunera Jamal; Syed Adnan Haider; Fahad Humayun; Qasim Ali; Rabia Hakim; Muhammad Salman; Massab Umair (Archives of Virology, 2026)

Investigation of Metabolites and Mineral Content in Blood Serum of Dairy Cows of the Simmental Breed in Samsun Province During the Transition Period - Neslihan Ormancı; Bora Bölükbaş; Muhammad Waqas; Mustafa Salman; Rıfat Pak; Doğukan Topal; Adnan Vehapoğlu (Biological Trace Element Research, 2026)

CO₂ stripping from amine solutions using PES hollow fiber membrane contactors - Muhammad Waseem; Muhammad Salman Shah; Nayef Ghasem; Mohamed Al-Marzouqi (Journal of Environmental Chemical Engineering, 2026)

Classification of clay bricks using vision-based machine learning algorithms - Muhammad Faizan; Muhammad Salman; Muhammad Noman; Ali Akhtar; Afaq Ahmad; Matiullah Bakhtyar (Innovative Infrastructure Solutions, 2026)

Predicting fire resistance of reinforced concrete (RC) and concrete-filled steel tubular (CFST) columns through machine learning - Muhammad Noman; Muhammad Salman; Mati Ullah; Muhammad Faizan; Afaq Ahmed (Innovative Infrastructure Solutions, 2026)

Optimizing sustainable agricultural production under uncertainty: a multi-objective model for crop selection and land allocation - Musawer Zeb; Waqas Ahmed; Muhammad Moazzam; Salman Sagheer Warsi; Muhammad Salman Habib (Environment, Development and Sustainability, 2026)

Green productivity and energy transition under china’s belt and road policy: a geopolitical perspective - Muhammad Salman (Environment, Development and Sustainability, 2026)

Tectonic and metallogenic processes along the east Tethyan metallogenic domain (Lhasa-southern Tibet, Kohistan island arc and Chagai magmatic belt): a perspective review - Muhammad Hafeez; Xiaoyong Yang; Ahmed Shah; Ibrar Khan; Zahra Abbasi; Salman Ahmed Khattak; Gendenjamts Baatar (International Geology Review, 2026)

Fermentation-enhanced functional properties of beetroot: From bioactive compounds to novel food products - Muhammad Salman Farid; Łukasz Łopusiewicz (Trends in Food Science & Technology, 2026)

Experimental insights on CIRLEM: Enhancing energy efficiency and flexibility in buildings - Mohammad Hosseini; Panayiotis Papadopoulos; Muhammad Salman Shahid; Kavan Javanroodi; Silvia Erba; Etta Grover-silva; Peter Riederer; Amin Moazami; Frederic Wurtz; Benoit Delinchant; Salvatore Carlucci; Mohammadreza Aghaei; et al. (Energy and Buildings, 2026)

Assessing debris-covered glaciers using geospatial techniques in the Hindu Kush Region, Pakistan - Shakeel Mahmood; Fatima Salman; Mariam Sarwar; Muhammad Irfan Ahamad (Cold Regions Science and Technology, 2026)

Effects of Moringa oleifera and Saccharomyces cerevisiae on growth performance, meat quality, and fatty acids profile of meat in broiler chickens - Noor Ahmad Nastoh; Mustafa Salman; Muhammad Waqas (Tropical Animal Health and Production, 2026)

Targeting gasdermin D–mediated pyroptosis: a precision anti-inflammatory strategy for acute and chronic lung diseases - Vijaya Paul Samuel; Muhammad Afzal; M. Arockia Babu; H. Malathi; Laxmidhar Maharana; Surya Nath Pandey; Haider Ali; Waleed Hassan Almalki; Salem Salman Almujri; K. Benod Kumar (Inflammopharmacology, 2026)

China eco-economic transition policy toward carbon neutrality: the role of renewable energy resources - Muhammad Salman Ahmad; Shabeer Khan; Fouzia Amin; Mirzat Ullah (Environment, Development and Sustainability, 2025)

Performance comparison of complete mix reactor and static mixer in ballasted flocculation - Muhammad Qasim; Muhammad Naveed Afridi; Salman Ali Suhail; Usman Pervaiz Khan; Imtiaz Afzal Khan; Jong-Oh Kim (Chemosphere, 2025)

A novel hybrid MOF–metal oxide electrochemical sensor for ultra-trace detection of cadmium ions - Sabah Haider; Mujahid Mustaqeem; Maria Zaib; Mohammed Ashraf Gondal; Umar Farooq; Muhammad Salman; Rabia Akram Bajwa (Journal of Environmental Chemical Engineering, 2025)

Solubility measurements of R143a, R23 and R116 with [HMIM][TF2N] and [BMIM][BF4] - Nimra Javed; Muhammad Salman; Yiran Wang; Peiji Wang; Asim Shakeel; Xiangyang Liu; Maogang He (International Journal of Refrigeration, 2025)

Mixed convective heat transfer enhancement in hybrid nanofluid flow through complex-finned tube cavities - Noreen Sher Akbar; Salman Akhtar; Shakil Shaiq; Muhammad Fiaz Hussain; Taseer Muhammad; M. Farooq; M. Bilal Habib (Dynamics of Atmospheres and Oceans, 2025)

Isolated and combined toxicity of PVC microplastics and copper on Pinctada fucata martensii: Immune, oxidative, and metabolomics insights - Robert Mkuye; Xiuyan Yang; Chuangye Yang; Edna Bubelwa; Fortunatus Masanja; Hagai Nsobi Lauden; Muhammad Salman; Yuewen Deng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Impact of Tannery Effluents on Groundwater Quality and Human Health in Kasur, Pakistan - Mohammad Salman Faisal; Muhammad Awais; Rohina Bashir; Muhammad Bilal Shakoor; Rizwan Aziz; Muhammad Rizwan; Affaq Ali; Simal Akhtar; Noor Fatima (Water, Air, & Soil Pollution, 2025)

Smart and Sustainable Microplastic Removal: Hybrid Systems, Bio-Inspired Technologies, Real-Time Sensing, and Policy Integration - Salman khan; Umme Kalsoom; Muhammad Kashif; Syed Aamir Hussain; Misbah Gul; Shohreh Azizi; Malik Maaza (Water, Air, & Soil Pollution, 2025)
The pervasive accumulation of microplastics in aquatic ecosystems has emerged as a critical global environmental challenge with profound implications for biodiversity, food safety, and human health. Conventional remediation approaches often fail to address microplastics' complex physiochemical diversity and resilience. In recent years, hybrid and bio-inspired technologies have emerged as promising alternatives for efficient microplastic remediation. This review critically examines the state-of-the-art hybrid systems comprising synergetic combinations of physical, chemical, and biological processes and bio-inspired approaches that mimic natural filtration, adhesion, and degradation mechanisms. Emphasis is placed on membrane-based hybrids, nature-mimicking adsorbents, and enzyme-functionalized materials and microrobots, as well as recent advances in smart monitoring systems and sensor technologies for real-time detection. Additionally, the review highlights the importance of integrated policies and technological synergies, stressing the need for harmonized regulatory frameworks and cross-sector collaboration to enable scalable and sustainable solutions. By integrating interdisciplinary insights, this work positions hybrid, bio-inspired and data-informed strategies at the forefront of sustainable solutions for microplastic remediation, paving the way toward cleaner ecosystems and circular plastic economies.

Carbon Nanotubes Improve Quantitative and Qualitative Attributes of Potato (Solanum tuberosum L) Genotypes - Muhammad Ismail; Muhammad Imtiaz; Raham Sher Khan; Fazal Jalal; Fazal Said; Muhammad Ali Khan; Syed Hussain; Badshah Islam; Salman Khan; Sabir Khan; Atta Ullah; Maqsood Khan; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Endophyte Bacterial Metabolites: An Active Syrup for Improvement of Growth, Biomass, and Antioxidant System of Zea mays L. in Drought Condition - Mahwish Salman; Muhammad Rizwan Javed; Anam Tariq; Muhammad Usama; Hafiza Iqra Hanif; Bushra Sadia; Shazia Naheed (Journal of Plant Growth Regulation, 2025)

Halotolerant Bacillus Aryabhattai Strain PM34 Mitigates Salinity Stress and Enhances the Physiology and Growth of Maize - Muhammad Atif Azeem; Salman Khan; Fawad Ali; Sajjad Ahmad; Gul Rahim; Muhammad Iftikhar; Majid Iqbal; Rawa Saad Aljaloud; Khaloud Mohammed Alarjani; Hassan Javed Chaudhary (Journal of Plant Growth Regulation, 2025)

Predicting axial load capacity of CFRP fire-damaged RC columns through DANN - Muhammad Noman; Muhammad Yaqub; Muhammad Salman; Muhammad Faizan; Shakouri Mahmoudabadi; Afaq Ahmad (Innovative Infrastructure Solutions, 2025)
This paper presents the results of a deep neural network (DNN) model predicting the axial load-carrying capacity of fire-damaged concrete square and rectangular reinforced concrete columns subsequently repaired using carbon fiber-reinforced polymer (CFRP) composites. An experimental database comprising 143 column specimen samples was collected from the literature. Thirteen parameters were noted, including Length of Columns (mm), Width of Columns (mm), Corner Radius (mm), Height of Column (mm), Initial Compressive Strength of Concrete (MPa), Initial Tensile Strength of Steel (MPa), Longitudinal Reinforcement Ratio (As/Ag, %), Temperature of Fire (°C), Fire Exposure Time (Minutes), Number of Layers of CFRP(Count), Thickness of CFRP (mm), and Tensile Elastic Modulus of CFRP (GPa). These parameters served as inputs for the model, with the final axial compressive strength of the CFRP-repaired column considered as the target/output. DNN models were calibrated for numerous numbers of neurons in the hidden layers to achieve optimization. The proposed DNN model demonstrated strong agreement with the experimental database, exhibiting an overall correlation factor (R) of 0.99946. The predicted outcomes of the proposed model closely align with the experimental findings, as evidenced by a thorough comparison with prior experimental investigations. Consequently, this model holds potential value for engineers seeking speedy assistance in repairing fire-damaged structures using CFRP composites.

Cutting edge: ferroptosis in metabolic dysfunction-associated steatotic liver disease (MASLD) pathogenesis and therapy - Amr Ali Mohamed Abdelgawwad El-Sehrawy; Teeba Ammar Rashid; Muhammad Ikram Ullah; Subasini Uthirapathy; Subbulakshmi Ganesan; Abhayveer Singh; Anita Devi; Kamal Kant Joshi; Ahmed Salman Jasim; Abed J. Kadhim (Functional & Integrative Genomics, 2025)

Revolutionizing energy and logistics: a multilayered strategy for optimizing distribution networks and achieving dual carbon goals - Sajad Ali; Min Yongzhi; Chen Xin; Jalalud Din; Muhammad Salman (Clean Technologies and Environmental Policy, 2025)

Microfacies analysis and depositional environment of Eocene Chorgali formation at Khanpur Dam Road Section, Hazara Basin, Pakistan - Bilal Shah; Syed Mamoon Siyar; Salman Khurshid; Dicky Muslim; Raden Irvan Sophian; Zahid Ullah; Abdul Wahid Asykarulloh; Asad Muhammad; Syed Muhammad; Wasim Sajjad (Carbonates and Evaporites, 2025)

Chitosan induces water deficit stress tolerance in Gladiolus grandiflorus via regulating water relations, gaseous exchange traits, and antioxidative defense - Muhammad Rizwan; Gulzar Akhtar; Muhammad Asif Shehzad; Salman Aloufi; Suliman Mohammed Suliman Alghanem; Faisal Zulfiqar; M. Nasir Khan; Özhan Şimşek; Fahad Al-Asmari; Mehmet Tütüncü; Tolga İzgü; Lala Gurbanova (Plant Biosystems, 2025)

Impact of COVID-19 on the prevalence of multi-drug-resistant bacteria: a literature review and meta-analysis - Haseeb Ahmed; Zain Ul Abideen; Ammar Azmat; Muhammad Irfan; Salman Anjum; Afaf Dirie (Antonie van Leeuwenhoek, 2025)

Analysis of natural resource efficiency convergence in global North and South: The role of artificial intelligence and geopolitical risks in club formation - Muhammad Salman; Guimei Wang (Environment, Development and Sustainability, 2025)

Spatio-temporal variability study of Shigar Basin Glaciers, Central Karakoram Region, Pakistan - Salman Mustafa; Faisal Rehman; Adnan Shafiq Rana; Tahir Azeem; Omar Riaz; Muhammad Fahad Ullah; Jamil Siddique; Faisal Rehman (Environmental Monitoring and Assessment, 2025)

Ethical AI: Human-centered approaches for adaptive and sustainable urban planning and policy - Mir Muhammad Nizamani; Salman Qureshi; Mahsa Tarashkar; Hai-Li Zhang; Qin Zhou; Zhongping Lai (Land Use Policy, 2025)

Germany’s energy security strategy in times of turmoil: The role of AI-driven energy systems and environmental policy in the Russian gas exit - Muhammad Salman (Energy Policy, 2025)

Designing MgAlCe-Adenine LDH@g-C3N4 nanohybrid integrated polypropylene for bi-functional flame retardancy and corrosion protection - Salman Khalid; Jun Sun; Xinyu Chen; Mohammad Tabish; Mubashar Mahmood; Muhammad Mubeen; Yangming Zou; Zhenhua Wang; Xiaoyu Gu; Jingmao Zhao; Ghulam Yasin; Sheng Zhang (Chemical Engineering Journal, 2025)

Mathematical models for fluid flow in porous media with machine learning techniques for landfill waste leachate - Muhammad Sulaiman; Muhammad Salman; Ghaylen Laouini; Fahad Sameer Alshammari (Stochastic Environmental Research and Risk Assessment, 2025)

Exploring the feasibility of construction and demolition waste recycling in an emerging Indian city using a dynamic modeling approach - Namya Sharma; Deepjyoti Das; Pradip P. Kalbar; Muhammad Salman (Journal of Industrial Ecology, 2025)
In emerging economies like India, infrastructure development is expected to grow in the coming decades. Buildings, an important infrastructural asset and anthropogenic material source, need adequate exploration as potential raw material repositories. This study introduces a novel “ Ma terial F L ow and market B ehavior A ssessment (MaLBA)” model to evaluate building material circularity prospects while integrating dynamic stock modeling for material flow and the Bass diffusion model for market maturity. The MaLBA model studies the feasibility of construction and demolition waste (CDW) recycling at the regional scale for Thane City, India, and highlights the influence of marketing mechanisms such as advertisement and word of mouth in recycled CDW product adoption at the regional scale. The model predicts a 20% decadal increase in CDW generation in the region, while the material required for new construction activities in Thane is expected to correspondingly rise by 13% between 2024 and 2050. Considering the present Indian policies focus on CDW recycling as the major CDW management strategy, the MaLBA model suggests that expanding Thane's recycling capacity from 300 to 700 Mt/Day can prove counterproductive to meet the national targets as the technical limitations of recycled material usage and limited user acceptance might lead to an oversupply of recycled CDW products by 2050. Therefore, this study recommends focusing on market development by doubling efforts to advertise recycled products and expand recycling infrastructure in alignment with regional infrastructure growth. Additionally, this study also suggests diversifying the CDW management approach by including strategies such as reduce and reuse for long‐term benefits.

Inverse Analysis of Pressuremeter Tests by Calibrating Soil Parameters for Toronto Sands - Muhammad Salman Babar; Jinyuan Liu (Geotechnical and Geological Engineering, 2025)

Evaluating Tunnel Squeezing in the Lawi Hydropower Project, Chitral, Pakistan: Geological and Empirical Perspectives - Muhammad Tariq Niaz; Waqas Ahmed; Shah Faisal Khattak; Jehanzeb Khan; Luqman Ahmad; Ihtisham Islam; Salman Ahmed Khattak (Geotechnical and Geological Engineering, 2025)

Thermal Thresholds and Mechanical Behavior of Granitic Rocks from Northern Pakistan: Implications for Rock Engineering - Abdul Rahim Asif; Muhammad Sajid; Waqas Ahmed; Ihtisham Islam; Abid Nawaz; Salman Ahmed Khattak (Geotechnical and Geological Engineering, 2025)

Phenological and morphological adaptations of Japanese quince (Chaenomeles japonica—(Thunb.)Lindl. ex Spach.) [Rosaceae]: insights from palynology and leaf histology - Shoxista Samatova; Mirtemir Berdiyev; Babir Baysunov; Muhammad Zafar; Salman Majeed; Mohamed Fawzy Ramadan; Trobjon Makhkamov; Muhammad Rizwan Khan; Khawaja Shafique Ahmad; Qamar Abbas; Ankeela Pńisyer; Fakhr ul Islam (Genetic Resources and Crop Evolution, 2025)

Assessing the genetic structure of olive cultivars in Mansehra, Pakistan for improved crop production - Ibrahim Khan; Shabnam Niaz; Muhammad Zafar; Salman Majeed; Eman Alhomaidi; Maha Aljabri; Trobjon Makhkamov; Nasibakhon Naraliyeva; Akramjon Yuldashev; Dilnoza Sotiboldiyeva; Zulunov Islom; Aneta A. Ptaszyńska (Genetic Resources and Crop Evolution, 2025)

Pollen as an insect interaction marker: palynological, chemical, and microscopic perspectives of selected medicinal plants - Nozimova Aziza Baxtiyorovna; Xaydarov Khislat Qudratovich; Djumayeva Zamira; Mohamed Fawzy Ramadan; Norkulov Ma’sudjon Ma’rufovich; Dilaro Fayzullayeva Botirjon Qizi; Ochilov Ulugbek Abdukhamidovich; Matkarimova Gulnaz Maqsudjanova; Nurullayeva Nodira Sayfullayevna; Muhammad Zafar; Salman Majeed; Muhammad Rizwan Khan; et al. (Genetic Resources and Crop Evolution, 2025)

Palynology as a taxonomic tool in the identification of riparian Moraceae species - Muhammad Rizwan Khan; Muhammad Zafar; Salman Majeed; Trobjon Makhkamov; Nasibakhon Naraliyeva; Inomjon Bakhramov; Sobhay M. Ibrahim; Munira Inomova; Bakhtiyor Rakhimov; Aneta A. Ptaszyńska (Genetic Resources and Crop Evolution, 2025)

Uncovering the oxidative stress and hematological consequences of chronic cobalt exposure on atherosclerosis - Rashad Ibragimov; Rovshan Khalilov; Fidan Nuriyeva; Ilgiz Gareev; Ozal Beylerli; Sergey Roumiantsev; Muhammad Zafar; Deema Kamal Sabir; Salman Majeed; Muhammad Rizwan Khan; Aleena Gul; Jonida Biturku (BioMetals, 2025)

Lab-scale catalytic hydrotreating of hydrothermal biocrude: Effects of temperature and space velocity on fuel upgrading and catalyst performance - Abdenour Achour; Daniele Castello; Muhammad Salman Haider; Lasse Aistrup Rosendahl (Chemical Engineering Journal, 2025)

Correction: Multivariate and Association Analyses of Various Seed Yield Contributing Traits Divulge Genetic Diversity Among Pisum sativum L. Genotypes - Noshi Parveen; Shamim Umer; Changwei Tan; Abdul Jabbar; Bilqees Kanwal; Imran Haider; Waqas Raza; Anwer Usma; Aqib Mahmood; Muhammad Bilawal Junaid; Salman Haidar Abbasi; Alanoud T. Alfagham; et al. (Plant Molecular Biology Reporter, 2025)

Multivariate and Association Analyses of Various Seed Yield Contributing Traits Divulge Genetic Diversity Among Pisum sativum L. Genotypes - Noshi Parveen; Shamim Umer; Changwei Tan; Abdul Jabbar; Bilqees Kanwal; Imran Haider; Waqas Raza; Anwer Usma; Aqib Mahmood; Muhammad Bilawal Junaid; Salman Haidar Abbasi; Alanoud T. Alfagham; et al. (Plant Molecular Biology Reporter, 2025)

Managing water deficit in wheat through mulches and irrigation techniques in semi-arid regions - Salman Ahmad; Muhammad Aown Sammar Raza; Muhammad Ali; Rashid Iqbal; Muhammad Usman Aslam; Monika Toleikiene; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Imran Haider; Muhammad Zain; Saltanat Aghayeva; Ozhan Simsek; et al. (Cereal Research Communications, 2025)

Seeds of the mountain: Investigating micromorphology and its impact on ecological sustainability - Bushra Ali; Muhammad Zafar; Salman Majeed; Modhi O. Alotaibi; Trobjon Makhkamov; Nasibakhon Naraliyeva; Rustamjon Allaberdiev; Khislat Khaydarov; Zulunov Islom; Enkelejda Kucaj (Journal of Mountain Science, 2025)

Flower-like nanoscale Ni(OH)2/MnCO3 electrocatalyst for efficient hydrogen evolution reaction in wide pH range - Zobia Siddique; Salman Noshear Arshad; Muhammad Ali Ehsan; Faryal Aftab; Akhtar Munir; Suryyia Manzoor; Sadia Fatima; Farah Sajjad; Javed Ahmad; Hatice Duran; Senem Çitoğlu (Fuel, 2025)

Assessing Human-Wildlife Conflict in Lakki Marwat, Pakistan: Economic Impacts and People’s Perceptions - Tanveer Khan; Shakeel Ahmad; Tahir Mehmood; Sajjad Rais Khan; Daulat Ullah Khan; Salman Khan; Muhammad Ullah; Ejaz Rahim (European Journal of Wildlife Research, 2025)

Long-term PM2.5 exposure in Bangladesh: identification of pollution hotspots, trends, sources and health risk assessment - Md. Arfan Ali; Mazen E. Assiri; Muhammad Bilal; Salman Tariq; Gerrit de Leeuw; M. Nazrul Islam; Yu Wang; Lama Alamri; Ayman S. Ghulam; Shamsuddin Shahid (Air Quality, Atmosphere & Health, 2025)

Exploring single-atom catalysis for hydrogen evolution and storage: A DFT insight into first-row transition metal-porphyrin complexes (Porph@TMs) - Faheem Abbas; Saleem Nawaz Khan; Sadaf Bibi; Mariyum Yousaf; Francis Enujekwu; Muhammad Salman Khan; Sami Ullah; Mohammed Ali Assiri (Gas Science and Engineering, 2025)

When low-dimensional nanomaterials meet polymers: A promising configuration for flame retardancy and corrosion protection - Salman Khalid; Muhammad Mubeen; Mohammad Tabish; Muhammad Jawad; Muhammad Uzair Malik; H.M. Ahsen Ilyas; Mubashar Mahmood; Mohammed Mujahid Alam; Jun Sun; Ghulam Yasin (Chemical Engineering Journal, 2025)

Alkali-activation of copper slag: Characterization and mechanical properties of inorganic polymer binder - Dhiraj Surendra Mahajan; Sher Singh Meena; Salman Muhammad (Chemical Engineering Journal, 2025)

7β-(3-ethyl-cis-crotonoyloxy)-1α-(2-methylbutyryloxy)-3,14-dehydro-Z-notonipetranone (ECN) attenuates inflammation and oxidative stress via MAPK, and Nrf2/HO-1 signaling in Traumatic brain injury - Sana Zafar; Maryam Jamil; Muhammad Ibrar Khan; Fakhar ud Din; Eun Kyoung Seo; Salman Khan (Chemico-Biological Interactions, 2025)

Channel morphology of the Indus, and the growing risk of floods related damages in the Indus River basin - Raveen Fatima; Salman Atif; Monique Fort; Muhammad Azmat (Natural Hazards, 2025)

Epidemiology and genetic characterization of Alternaria alternata causing leaf spot in Fragaria × ananassa - Nasir Mehmood; Abid Riaz; Salman Ghuffar; Sadaf Anwaar; Nyla Jabeen; Isha Shaheen; Muhammad Qasim; Salma Saeed Khan; Muhammad Rauf; Tauseef Anwar; Huma Qureshi; Ghadah Salim Abusalim; et al. (Fungal Biology, 2025)

Tailoring g-C3N4 properties through P and K co-doping: advancing photocatalytic CO2 reduction to CH4 - Ahmed Ismail; Muhammad Zahid; Bilal Ahmad; Salman Hayat; Sher Ali; Syed ul Hasnain Bakhtiar; Abdullah N. Alodhayb; Xiaoqiang Wu; Qaisar Alam; Sharafat Ali; Liang Qiao (Chemical Engineering Journal, 2025)

Spatial, Trend, and Wavelet Analysis of AOD Over Bangladesh - Salman Tariq; Özgür Zeydan; Hafsa Shahzad; Muhammad Khan (Water, Air, & Soil Pollution, 2025)
With the rapid increase in urbanization and industrialization environmental degradation is one of the major issues of developing countries. During the last couple of years, Bangladesh has faced the poorest air quality due to this urbanization. Therefore, in this study, we used Moderate Resolution Imaging Spectroradiometer (MODIS) and Multi-angle Imaging Spectro Radiometer (MISR) retrieved Aerosol optical depth (AOD) data to investigate the spatial–temporal distribution, trend analysis, and the periodic nature of AOD over Bangladesh during the monsoon season from 2003 to 2016. Moreover, we used the Mann–Kendall test and Sen’s slope to analyze the trend analysis of aerosol during monsoon season. We also used wavelet coherence analysis (CWT) and Continuous wavelet transform (CWT) function to observe the periodic correlation of AOD with different meteorological parameters i.e., evapotranspiration, latent heat flux, precipitation, relative humidity, wind speed, and surface air temperature. The average MODIS and MISR retrieved AOD showed an increasing trend in the western regions of Bangladesh with an average value ranging from 0.27 to 0.92 and 0.13 to 0.59 respectively. AOD showed minimum values in Chittagong divisions and tends to increase towards the western region of Bangladesh. Furthermore, we observe the insignificant AOD trend during monsoon season due to high precipitation levels during June and July that washout the aerosol. Moreover, the annual variability of average AOD showed the maximum concentration of aerosols in 2008 and while minimum during 2015. Furthermore, CWT of MODIS retrieved AOD and MISR retrieved AOD shows a strong periodicity (> 0.9) during the 2nd to 4th period. MODIS AOD and MISR AOD also show a series of leading, lagging, in-phase, and anti-phase situations for all years 2003–2016, having a strong cross-wavelet transform (XWT) power ranging from 0.0 to 1. Different techniques, such as afforestation, efficient fuel usage, the development of public transport networks, etc., would be employed in light of the study’s findings to lower the concentration of particle pollution.

Unveiling the power of PavGID1s: the critical player in sweet cherry flower bud dormancy release - Xunju Liu; Li Wang; Muhammad Aamir Manzoor; Wanxia Sun; Yan Xu; Muhammad Salman Haider; Zhengxin Lv; Jiyuan Wang; Ruie Liu; Songtao Jiu; Caixi Zhang (Plant Molecular Biology, 2025)

Exploring Synergistic Effects of Pantoea agglomerans BCH-1 and Bacillus pseudomycoides BCH-3 To Enhance Maize Adaptations Under Drought Condition - Anam Tariq; Mahwish Salman; Muhammad Arslan Ashraf; Shazia Anwer Bukhari; Ghulam Mustafa (Journal of Soil Science and Plant Nutrition, 2025)

Hydrocarbon generation potential of the lower Jurassic-Eocene intervals in the Potwar Plateau, Pakistan: insights from organic geochemical, 1D basin modeling and petrographic analysis - Masood Shah; Syed Mamoon Siyar; Abbas F. Gharib; Iman M. Anwer; Muhammad Irfan; Mohammad Salman Shamim; Nasar Khan; Taqweem Ul. Haq; Yasir Hamid; Kamran Shams (Carbonates and Evaporites, 2025)

Halophytic palynomorphs morphology unraveling the links between palynology and aerobiology - Kashif Jamal; Muhammad Zafar; Khalid Mashay Al-Anazi; Mohammad Abul Farah; Nasibakhon Naraliyeva; Khislat Khaydarov; Fethi Ahmet Özdemir; Kholmurod Zhalov; Nozimova Aziza; Salman Majeed; Zulunov Islom; Muhammad Rizwan Khan; et al. (Aerobiologia, 2025)

Digital twins: cornerstone to circular economy and sustainability goals - Zain Anwar Ali; Mahreen Zain; Raza Hasan; Muhammad Salman Pathan; Hussain AlSalman; Faisal Abdulaziz Almisned (Environment, Development and Sustainability, 2025)
Accurate information is a prerequisite for circulation and greater longevity of materials and products, enabling the economically and environmentally successful transition of circular economy (CE) in the aspiration towards sustainable development. However, a lack of appropriate digital tools is noticed in supplying relevant information and supporting recyclability, reusability, and reducibility processes. This study focuses on a building block of evolving technologies anointed the digital twin (DT). It aims to conceptualize DT as a cornerstone for the CE paradigm, positively influencing sustainability. It also endeavors to scrutinize remarkable implementations of DT-driven CE, accomplishing sustainable development goals (SDGs) in Ireland. An iterative methodology based on four steps is adopted to review an explosion of relevant, recent literature published in 2019–2024 and multiple case studies of Irish construction and manufacturing sectors. By analyzing the literature, this study discovers the evolution and taxonomy of DT, other technologies essential for its deployment, its proactive role in implementing CE and SDGs, and some challenges. Key findings of case studies reveal the current trajectory of employing DT with other digital products, upholding the CE practices within the bounds of the SDGs in Irish companies. In conclusion, DT is a conceivable means for advancing CE solutions and attaining SDGs towards social, economic, and environmental sustainability. The implications of this study are both theoretically and practically significant, encouraging industrialists and academia to adopt DT. It will help scholars gain a thorough understanding and guide industrialists to downsize their carbon footprint and waste, accomplishing SDGs. It will inspire managers with DT-driven information for decision-making and facilitate government and policymakers to collaborate in designing essential policies. Graphical Abstract

A survey of quantifying food waste from hotel restaurants and caterers in Multan, Southern Punjab, Pakistan - Abdul Basit; Nida Urooj; Muhammad Humza; Muhammad Salman Hameed (Food and Humanity, 2025)

Exploring economic and cargo efficiencies in the global shipping sector: A convergence analysis - Muhammad Salman (Journal of Cleaner Production, 2025)

From waste to resource: Life cycle assessment of eco-friendly concrete in developing nations through energy transition - Yousaf Ali; Muhammad Salman Hassan; Antonella Petrillo (Journal of Cleaner Production, 2025)

Assessment of variability in chlorophyll-a and covariates in East/Japan sea: New insights from the ARIMAX model and wavelet coherence - Salman Tariq; Ayesha Mariam; Muhammad Khan (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

ENSO teleconnections and predictability of the boreal summer temperature over the Arabian Peninsula in C3S and Saudi-KAU seasonal forecast systems - Mansour Almazroui; M. Salman Khalid; Muhammad Adnan Abid; Irfan Ur Rashid; Shahzad Kamil; Haroon Siddiqui; M. Nazrul Islam; Muhammad Ismail; Muhammad Azhar Ehsan; Enda O'Brien; Mazen Asiri; Rayees Ahmed; et al. (Atmospheric Research, 2025)

Pollen patterns and morphological variability unraveling cyperaceae diversity through palynological traits - Umber Rubab Niazi; Muhammad Zafar; Abdullah Ahmed Al-Ghamdi; Bandar Mohsen Almunqedhi; Trobjon Makhkamov; Norimova Guljakhon Abduganievna; Inomjon Bakhramov; Kholmurod Zhalov; Islombek Anvarbekov; Gulhayo Yaxshibekova; Salman Majeed; Shaista Jabeen; et al. (Genetic Resources and Crop Evolution, 2025)

Spatio-temporal analysis of PM2.5 and its association with elevation by using remote sensing: the scenario of Quetta, Pakistan - Laraib Ehtasham; Malik Muhammad Akhtar; Salman Tariq; Ishaq Ahmad Mian (Air Quality, Atmosphere & Health, 2025)

Validation of two multiplex lateral flow devices for the rapid detection and typing of foot-and-mouth disease viruses - Efrem Alessandro Foglia; Valerie Mioulet; Simone Cavalera; Jozhel Baguisi; Sena İnel Turgut; Abraham Sangula; Salman Khan; Syed Muhammad Jamal; Harry Bull; Sergio Rosati; Chiara Nogarol; Giulia Pezzoni; et al. (Research in Veterinary Science, 2025)

Retraction notice to “Bio-mitigation of organic pollutants using horseradish peroxidase as a promising biocatalytic platform for environmental sustainability” [Environ. Res. 239-P1 (2023) 117192] - Muhammad Bilal; Anil Kumar Singh; Hafiz M.N. Iqbal; Tak H. Kim; Grzegorz Boczkaj; Khawlah Athmaneh; Syed Salman Ashraf (Environmental Research, 2025)

Fronds micromorphology of anatomical parameters among selected ferns species in Uzbekistan - Dilshodjon Muminov; Khislat Khaydarov; Muhammad Zafar; Humaira Rizwana; Mohamed Soliman Elshikh; Trobjon Makhkamov; Salman Majeed; Islamov Boston Sultanovich; Ilkhom Mukumov; Zebiniso Umurzakova; Murtoza Hasanov; Zebo Rasulova; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Role of Melatonin in Leaf Gas Exchange by Redox Regulation, K+ Homeostasis and Gene Expression in Canola Under Salinity Stress - Muhammad Ali; Muhammad Farooq; Adnan Noor Shah; Ghulam Hassan Abbasi; Salman Ahmad; Aasma Parveen; Birhanu Iticha; Muhammad Riaz; Muhammad Kamran; Fatima Nisar (Journal of Soil Science and Plant Nutrition, 2025)

Significance of Selenium in Improving the Yield and Quality of Quinoa Under Drought - Muhammad Usman Aslam; Muhammad Aown Sammar Raza; Rashid Iqbal; Salman Ahmad; Imran Haider; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Saltanat Aghayeva; Nazim S. Gruda (Journal of Soil Science and Plant Nutrition, 2025)

Palynological characterization of selected herbaceous plants in the lesser Himalaya of Azad Jammu and Kashmir - Aroosa Habib; Muhammad Zafar; Khalid Mashay Al-Anazi; Mohammad Abul Farah; Mushtaq Ahmad; Trobjon Makhkamov; Salohiddinjon Yunusov; Aneta A. Ptaszyńska; Naile Aliyeva; Salman Majeed; Omer Kilic; Iqra Qayyum; et al. (Genetic Resources and Crop Evolution, 2025)

Pollen morphology of some Nepeta L. Taxa in Uzbekistan - Trobjon Makhkamov; Abdurashid Rahmatov; Muhammad Zafar; Mohamed S. Elshikh; Dunia A. Al Farraj; Akramjon Yuldashev; Sokhib Islamov; Dilnoza Sotiboldiyeva; Zokirjon Makkamov; Dilabza Khakimova; Rustamjon Allaberdiev; Aneta A. Ptaszyńska; et al. (Genetic Resources and Crop Evolution, 2025)

Pharmacological properties of Hoya (Apocynaceae): a systematic review - Muhammad Khairil Rumaling; Siat Yee Fong; Pasupuleti Visweswara Rao; Johnny Gisil; Mohd Hijaz Mohd Sani; Wan Salman Wan Saudi (Natural Product Research, 2025)

Spatial effect decomposition of new-type urbanization on green development efficiency in China: based on an improved spatial DID model - Guimei Wang; Muhammad Salman (Environment, Development and Sustainability, 2025)

A review of recent advances in green and sustainable technologies for removing 4-nitrophenol from the water and wastewater - Hamza Badamasi; Zain Naeem; Giorgio Antoniolli; Avvaru Praveen Kumar; Abdul Ademola Olaleye; Ismail Shina Sadiq; Naseer Inuwa Durimin-iya; Muhammad Salman Khan (Sustainable Chemistry and Pharmacy, 2025)

An integrated photocatalytic redox architecture for simultaneous overall conversion of CO2 and H2O toward CH4 and H2O2 - Muhammad Salman Nasir; Bowen Sheng; Ying Zhao; Haotian Ye; Jun Song; Jinglin Li; Ping Wang; Tao Wang; Xinqiang Wang; Zhen Huang; Baowen Zhou (Science Bulletin, 2025)

A review of performance, mechanism, and challenges of layered double hydroxide-based biocomposites for the adsorptive removal of dye contaminants from water and wastewater - Salman Ahmad; Ghulam Mujtaba; Mukarram Zubair; Mansoor Ul Hassan Shah; Muhammad Daud; Nuhu Dalhat Mu'azu; Mamdouh A. Al-Harthi (Journal of Water Process Engineering, 2025)

Unveiling the potential of Loigolactobacillus coryniformis BCH-4 to ameliorate drought stress in Zea mays L. - Anam Tariq; Mahwish Salman; Muhammad Arslan Ashraf; Muhammad Rizwan Javed; Abdul Tawab (World Journal of Microbiology and Biotechnology, 2025)

Embryonic Temperature Influences the Mucosal Responses of Atlantic Salmon Alevins to a Bacterial Challenge - Muhammad Salman Malik; Alexander Rebl; Erik Burgerhout; Carlo C. Lazado (Marine Biotechnology, 2025)
The present work investigated the effects of embryonic temperature on the responses of Atlantic salmon ( Salmo salar ) alevins to a bacterial challenge using Yersinia ruckeri as a model pathogen. Embryos were reared at 4 °C, 6 °C, and 8 °C from fertilization to the eyed-egg stage. Alevins, before the start of feeding, were challenged with the pathogen, and mortality and early immune responses in mucosal organs were assessed. Fish from the 4 °C and 6 °C groups exhibited higher survival probabilities than those from the 8 °C group 72 h post-infection. Mild histopathological changes were observed in the gills and skin across all temperature groups, with bacterial antigen detected in the secondary lamellae of gills and in the skin epithelial and basal layers. Gene expression profiling revealed slightly distinct immune gene expression patterns in low-temperature groups (4 °C and 6 °C) compared to the 8 °C group. Gelsolin ( gsn ) expression increased in the skin across all temperature groups at 72 h post-infection. Claudin ( cldn4 ) and collagen ( col1a ) were only upregulated in the skin of the 4 °C group, while heat shock protein 70 ( hspa1a ) was downregulated in the gills of infected fish at 72 h compared to controls. Toll-like receptor 13 ( tlr13 ) expression increased in infected fish at 24 h compared to controls. In the 6 °C and 8 °C groups, gsn expression also increased at 72 h post-infection. Cldn4 expression increased only in the gills of 8 °C infected fish. This study revealed that low embryonic temperature could influence survival and mucosal immune defences following a bacterial challenge in Atlantic salmon alevins.

Foliar epidermal micromorphology: a contribution to the taxonomy of family Oleaceae - Tajalla Batool; Muhammad Zafar; Mohamed S. Elshikh; Abd El-Zaher M. A. Mustafa; Mushtaq Ahmad; Trobjon Makhkamov; Sokhib Islamov; Dilnoza Sotiboldiyeva; Akramjon Yuldashev; Mozaniel Santana De Oliveira; Salman Majeed; Inomjon Bakhramov; et al. (Genetic Resources and Crop Evolution, 2025)

Histological analysis of petiole structure in Euphorbiaceae species for taxonomic classification - Salman Majeed; Muhammad Zafar; Mohamed S. Elshikh; M. Ajmal Ali; Mushtaq Ahmad; Asif Mir; Trobjon Makhkamov; Mohammad Athar; Sokhib Islamov; Moona Nazish; Khislat Khaydarov; Maxsuda Nizomova; et al. (Genetic Resources and Crop Evolution, 2025)

The introduction of the SARS-CoV-2 BA.4 lineage into Pakistan - Zaira Rehman; Katherine Edington; Zunera Jamal; Angelika Kritz-Wilson; Gytis Dudas; Samuel Sims; Richard Myers; Babak Afrough; Leena Inamdar; Syed Adnan Haider; Aamer Ikram; Muhammad Salman; et al. (Archives of Virology, 2025)

Influence of pro-environmental behavior (PEB) on environmental sustainability: empirical evidence from health supplements industry - Faryal Salman; Muhammad Shahid Khan (Environment, Development and Sustainability, 2025)

Effect of bioactive compounds in processed Camellia sinensis tea on the intestinal barrier - Nan Chen; Peng Yao; Muhammad Salman Farid; Tiehua Zhang; Yangchao Luo; Changhui Zhao (Food Research International, 2025)

Potential interventions and interactions of bioactive polyphenols and functional polysaccharides to alleviate inflammatory bowel disease – A review - Muhammad Salman Farid; Bakhtawar Shafique; Rui Xu; Łukasz Łopusiewicz; Changhui Zhao (Food Chemistry, 2025)

Revolutionizing Fingerprint Detection: Ce3+ Doped SiO2-Zr2O3:Sr2+ Nanocomposites with Enhanced Luminescence and Selectivity - Momna Qayyum; Sammia Shahid; Sana Mansoor; Muhammad Faizan; Mohsin Javed; Ammar Zidan; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Abd-ElAziem Farouk; Salman Aloufi (Journal of Fluorescence, 2024)
Even though fingerprints remain one of the most reliable methods of identification, they are often lost during the recovery process. Accurate fingerprint recognition depends on the contrast between the ridges and substrate. On tough surfaces, such as glossy, colorful, and patterned materials, the contrast is harder to establish. Photoluminescent materials play a crucial role in forensic investigations as they enable the development of procedures that enhance image quality and increase the accuracy of findings from security institutions. Due to the strong emission in the red area at 620 nm, the use of trivalent Rare Earth ions (RE 3+ ) doped materials in this work is notable. Because of the unique properties and abundance of cerium, luminous materials based on SiO 2 -Zr 2 O 3 : Ce 3+ , Sr 2+ prepared via sol-gel technique present a more practical alternative for use in criminal investigations compared to current photonic materials. The sample was further co-doped with synthetic (Safranin-O and crystal violet) as well as organic (curcumin and lycopene) photoluminescent dyes. The nanocomposites were examined using X-ray diffraction analysis (XRD), energy-dispersive X-ray analysis (EDX), dynamic light scattering (DLS), scanning electron microscopy (SEM), and photoluminescence spectroscopy (PL). In conclusion, this work highlights the qualities critical to obtaining higher-resolution latent fingerprint images for potential forensic applications.

Health risk assessment of lead and cadmium exposure from food and snuff in Pakistani population - Hamza Shafiq; Mamoona Amir; Salman Asghar; Aneela Hameed; Muhammad Riaz (Journal of Trace Elements in Medicine and Biology, 2024)

Reply by the authors to the letter by S. Nadarajah - Muhammad Mohsin; Salman Abbas; Muhammad Mubeen Khan (Stochastic Environmental Research and Risk Assessment, 2024)

Effect of Bacillus subtilis Supplemented Diet on Broiler’s Intestinal Microbiota and TLRs Gene Expression - Salman Khan; Anam Khalid; Ru Yang; Fatima Khalid; Muhammad Hamza Zahid; Haozhe Liu; Yunhua Zhang; Zaigui Wang (Probiotics and Antimicrobial Proteins, 2024)

PPG2RespNet: a deep learning model for respirational signal synthesis and monitoring from photoplethysmography (PPG) signal - Md Nazmul Islam Shuzan; Moajjem Hossain Chowdhury; Saadia Binte Alam; Mamun Bin Ibne Reaz; Muhammad Salman Khan; M. Murugappan; Muhammad E. H. Chowdhury (Physical and Engineering Sciences in Medicine, 2024)

Successful application of modified crude DNA extraction from muscle tissues for various types of PCR amplifications - Sana Jafar; Salman Jamil; Muhammad Sheraz Yasin; Asif Naseem; Muhammad Yasir Zahoor; Wasim Shehzad; Muhammad Imran (Molecular Biology Reports, 2024)

Integrating morpho pollinic traits for systematic classification of rubiaceous species and conservation implications - Tariq Ullah; Muhammad Zafar; Mushtaq Ahmad; Jawaher Alkahtani; Mohamed Soliman Elshikh; Trobjon Makhkamov; Akramjon Yuldashev; Omer Kilic; Shazia Sultana; Salman Majeed; Oybek Mamarakhimov; Laziza Botirova; et al. (Genetic Resources and Crop Evolution, 2024)

Reliable attitude control integrating reaction wheels and embedded asymmetric magnetorquers for detumbling CubeSats - Shoaib Ahmed Khan; Zou Tao; Shah Fahad; Muhammad Salman; Mustafa Tahir; Anwar Ali (Advances in Space Research, 2024)

Impact of seismotectonic source zoning and seismic parameter: Sensitivity study on probabilistic seismic hazard assessment - Muhammad Salman Ali; Kashif Saeed; Luo Dong; Ma Jianxun (Soil Dynamics and Earthquake Engineering, 2024)

Retraction notice to “Hydrogen role in energy transition: A comparative review” [Process Saf. Environ. Prot. 184 (2024) 1069–1093] - Qusay Hassan; Sameer Algburi; Marek Jaszczur; Ali Khudhair Al-Jiboory; Tariq J. Al Musawi; Bashar Mahmood Ali; Patrik Viktor; Monika Fodor; Muhammad Ahsan; Hayder M. Salman; Aws Zuhair Sameen (Process Safety and Environmental Protection, 2024)

Erratum to “Improved project control for sustainable development of construction sector to reduce environment risks” [J. Clean. Product. (2019) 118214] - Summaira Malik; Fareena Fatima; Asma Imran; Lai Fatt Chuah; Jirí Jaromír Klemes; Imran Hameed Khaliq; Saira Asif; Muhammad Aslam; Farrukh Jamil; Abdullah Khan Durrani; Majid Majeed Akbar; Muhammad Shahbaz; et al. (Journal of Cleaner Production, 2024)

1-Dimensional metal Nitride-Supported platinum nanoclusters for Low-Temperature hydrogen production from formic acid - Liang Qiu; Bowen Sheng; Haotian Ye; Ping Wang; Jinglin Li; Ying Li; Yixin Li; Tianqi Yu; Muhammad Salman Nasir; Xinqiang Wang; Hu Pan; Zhen Huang; et al. (Chemical Engineering Journal, 2024)

Analyzing policy implications by considering adoption barriers on consumer adoption intention for electric vehicles: a comprehensive overview - Farheen Ehsan; Salman Habib; Muhammad Majid Gulzar; Junhua Guo (Environment, Development and Sustainability, 2024)

Balancing growth and sustainability: COP 28 policy implications of green energy, industrialization, foreign direct investment, and globalization in South Asia - Muhammad Asif; Nabila Amin; Muhammad Salman Shabbir; Huaming Song (Journal of Environmental Management, 2024)

Transition towards a low-carbon global economy: An integrated analysis of club convergence, catch-up and the agenda 2030 - Muhammad Salman; Guimei Wang; Xiaoqin Cui; Xing He (Gondwana Research, 2024)

Deciphering fungicide resistance in Phytophthora: mechanisms, prevalence, and sustainable management approaches - Syed Atif Hasan Naqvi; Muhammad Farhan; Muhammad Ahmad; Rafia Kiran; Noor Fatima; Muhammad Shahbaz; Muhammad Akram; Jaya Seelan Sathiya Seelan; Amjad Ali; Salman Ahmad (World Journal of Microbiology and Biotechnology, 2024)

Probabilistic modeling of extreme events involving decaying variables with an application in seismology - Muhammad Mohsin; Salman Abbas; Muhammad Mubeen Khan (Stochastic Environmental Research and Risk Assessment, 2024)

Flaxseed mucilage—a green additive for the enhancement of water-based mud system characteristics - Faiza Kanwal; Shaine Mohammadali Lalji; Syed Imran Ali; Muneeb Burney; Muhammad Ovais Tariq; Leena Hasan Ahmed; Umer Ahmed Khan; Aashan Sheikh; Muhammad Salman (Arabian Journal of Geosciences, 2024)

Understanding the spatiotemporal distribution of aerosols and their association with natural and anthropogenic factors over Saudi Arabia using multi-sensor remote sensing data - Muhammad Khan; Salman Tariq; Zia Ul Haq; Mehnaz Rashid (Air Quality, Atmosphere & Health, 2024)

Spatiotemporal changes in LULC and associated impact on urban Heat Islands over Pakistan using geospatial techniques - Zubair Irshad; Mujtaba Hassan; Salman Akbar; Muhammad Farooq; Farrukh A. Chishtie (Urban Climate, 2024)

G20 roadmap for carbon neutrality: The role of Paris agreement, artificial intelligence, and energy transition in changing geopolitical landscape - Muhammad Salman; Guimei Wang; Lin Qin; Xing He (Journal of Environmental Management, 2024)

Can urea-coated fertilizers be an effective means of reducing greenhouse gas emissions and improving crop productivity? - Muhammad Umair Hassan; Huang Guoqin; Muhammad Saleem Arif; Muhammad Salman Mubarik; Haiying Tang; Huifang Xu; Binjuan Yang; Quan Zhou; Awais Shakoor (Journal of Environmental Management, 2024)

Preparation, characterization and functional evaluation of soy protein isolate-peach gum conjugates prepared by wet heating Maillard reaction - Arif Hussain; Muhammad Hussain; Waqas Ashraf; Aiman Karim; Sahibzada Muhammad Aqeel; Adil Khan; Asif Hussain; Salman Khan; Zhang Lianfu (Food Research International, 2024)

Azotobacter Modulate Nitrogen Assimilation, Sustain Light Harvesting Efficiency and Photosynthetic Performance of Maize Cultivar in a Saline Soil - Komal Nida; Zamin Shaheed Siddiqui; Manzer H. Siddiqui; Zeeshan Ahmed Salman; Muhammad Umar (Journal of Soil Science and Plant Nutrition, 2024)

Sedimentology and reservoir characterization of Upper Cretaceous Kawagarh Formation, Upper Indus Basin, Lesser Himalayas, Pakistan: inferences from petrography, SEM-EDS and petrophysics - Salman Ahmed Khattak; Muhammad Hanif; Sajjad Ahmad; Ihtisham Islam; George Kontakiotis; Evangelia Besiou; Assimina Antonarakou (Carbonates and Evaporites, 2024)

Microbial biodiversity and plant functional trait interactions in multifunctional ecosystems - Mir Muhammad Nizamani; Alice C. Hughes; Salman Qureshi; Qian Zhang; Entaj Tarafder; Diptosh Das; Krishnendu Acharya; Yong Wang; Zheng-Guang Zhang (Applied Soil Ecology, 2024)

An Investigation of the Ultraviolet Aerosol Index and Angstrom Exponent and Their Relationship with Meteorological Parameters over Nigeria Using Satellite Remote Sensing - Muhammad Khan; Salman Tariq; Zia Ul Haq (Pure and Applied Geophysics, 2024)

Development of building stock model for an emerging city in India: Learnings for enabling circular economy in the built environment - Namya Sharma; Pradip P. Kalbar; Muhammad Salman (Journal of Industrial Ecology, 2024)
This study explores the prospects of urban mining for a steadily developing city “Thane,” located in the Mumbai Metropolitan Region of India, through building material stock accounting (BMSA). A novel bottom‐up approach for stock accounting was developed for the cities with limited data availability, through the integration of geodata spatial analysis, archetype identification through statistical modeling, and regional building design assessment for material intensity calculation. This study is the first of its kind in the Indian context and focuses on the stock estimation of the most common building materials: concrete, reinforcement steel, and masonry bricks within the boundaries of a typical Indian urban area. The results showed that the total built‐up stock in Thane city in 2018 amounts to 84.7 million metric ton (MT) by weight; concrete 57.7%, bricks 40.4%, steel 1.9%. Such reservoirs of raw material can be harnessed to fulfill the future material requirements of the construction industry through proposed circular economy interventions such as material bank creation, local recycling facilities, and development of a secondary material market. The material stock estimated in this study was 46.1 MT/capita for permanent building dwellers and with potential infrastructural developments underway, urban mining application can be ensured by redefining design and demolition strategies and multi‐level collaboration for generating alternative material sources for the construction sector. This work of BMSA intends to provide meaningful insights into exploring the potentials of urban mining and help chart the future roadmaps of sustainable construction in India.

Retraction Note: COVID-19 and stock exchange return variation: empirical evidences from econometric estimation - Yousaf Latif; Ge Shunqi; Shahid Bashir; Wasim Iqbal; Salman Ali; Muhammad Ramzan (Environmental Science and Pollution Research, 2024)

Retraction Note: The step towards environmental mitigation in Pakistan: do transportation services, urbanization, and financial development matter? - Danish Iqbal Godil; Paiman Ahmad; Muhammad Sajjad Ashraf; Salman Sarwat; Arshian Sharif; Syed Shabib-ul-Hasan; Kittisak Jermsittiparsert (Environmental Science and Pollution Research, 2024)

Unlocking plant secrets: A systematic review of 3D imaging in plant phenotyping techniques - Muhammad Salman Akhtar; Zuhair Zafar; Raheel Nawaz; Muhammad Moazam Fraz (Computers and Electronics in Agriculture, 2024)

Recent trends in fermented plant-based analogues and products, bioactive peptides, and novel technologies-assisted fermentation - Muhammad Salman Farid; Rameesha Anjum; Yiping Yang; Maoling Tu; Tao Zhang; Daodong Pan; Yangying Sun; Zhen Wu (Trends in Food Science & Technology, 2024)

Evaluating the impact of landscape configuration, patterns and composition on land surface temperature: an urban heat island study in the Megacity Lahore, Pakistan - Muhammad Nasar-u-Minallah; Dagmar Haase; Salman Qureshi (Environmental Monitoring and Assessment, 2024)

Classification of aerosol types in mega-city of Lahore (Pakistan) using ground-based remote sensing - Muhammad Nabeel Khan; Salman Tariq; Nimra Ehsan; Tunjeena Haseeb (Air Quality, Atmosphere & Health, 2024)

The flavors of edible mushrooms: A comprehensive review of volatile organic compounds and their analytical methods - Ruiyu Zhu; Yuxi Wen; Weihao Wu; Lizhu Zhang; Muhammad Salman Farid; Shuo Shan; Jiahui Wen; Mohamed A. Farag; Yuyu Zhang; Chao Zhao (Critical Reviews in Food Science and Nutrition, 2024)

Quantifying the role of logic tree parameters in soil probabilistic seismic hazard assessment: Insights from sensitivity analysis - Muhammad Salman Ali; Kashif Saeed; Luo Dong; Ma Jianxun (Soil Dynamics and Earthquake Engineering, 2024)

Florfenicol removal from veterinary pharmaceutical effluents: Tri-metallic zeolite 5A° for electrochemical oxidation and catalytic ceramic membrane separation - Amir Ikhlaq; Maryam Gull; Afnan Sajid; Khurram Saleem Joya; Muhammad Raashid; Osama Shaheen Rizvi; Zafar Masood; Salman Ahmed; Maryam Abid; Maham Hanif; Hafiz Abdul Aziz; Thamer Abdulhameed Al Johani; et al. (Journal of Environmental Chemical Engineering, 2024)

Uncovering the dynamics of atmospheric aerosols in China: A comprehensive analysis of OMI-Retrieved aerosol index data - Muhammad Khan; Salman Tariq (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Characterization of the tubby-like proteins (TLPs) gene family in Cucumis sativus L.: insights into the evolution, structure, and expression patterns under salt stress - Ikram Ullah; Muhammad Uzair; Obaid Ur Rehman; Safira Attacha; Kotb A. Attia; Sheraz Ahmad; Muhammad Salman; Hamid Ali; Muhammad Abdul Rehman Rashid; Asmaa M. Abushady; Sajid Fiaz; Syed Jehangir Shah; et al. (Genetic Resources and Crop Evolution, 2024)

Deep soil seismic hazard assessment: analyzing the impact of local site effects by stochastic site response analysis—a comparative approach - Muhammad Salman Ali; Kashif Saeed; Ma Jianxun; Luo Dong; Liaqat Ali (Bulletin of Engineering Geology and the Environment, 2024)

Clubroot (Plasmodiophora brassicae) Suppression Under Biocontrol Agents in Pak choi with Variations in Physiological, Biochemical, and Bacterial Diversity - Shazma Gulzar; Fiza Liaquat; Muhammad Khalid Hameed; Asad Rehman; Muhammad Salman Zahid; Muhammad Aamir Manzoor; Iftikhar Hussain Shah; Yidong Zhang (Journal of Plant Growth Regulation, 2024)

Development of a robust method for Cd(II) ions analysis using CeO2- and CeO2-Cu-BTC-based electrochemical sensors - Sabah Haider; Maria Zaib; Umar Farooq; Muhammad Salman; Rabia Akram Bajwa; Shabnam Shahida; Muhammad Aslam (Environmental Monitoring and Assessment, 2024)

Corrigendum to “Mimicking the cementation mechanism of ancient Roman seawater concrete using calcined clays” [Applied Clay Science 230 (2022) 106696] - Warda Ashraf; Ishrat Baki Borno; Rakibul I. Khan; Salman Siddique; Muhammad Intesarul Haque; Adhora Tahsin (Applied Clay Science, 2024)

Genomic characterization of human respiratory syncytial virus circulating in Islamabad, Pakistan, during an outbreak in 2022-2023 - Syed Adnan Haider; Zunera Jamal; Faheem Tahir; Muhammad Salman; Massab Umair (Archives of Virology, 2024)

From field to table: Ensuring food safety by reducing pesticide residues in food - Salman Munir; Asad Azeem; Muhammad Sikandar Zaman; Muhammad Zia Ul Haq (Science of The Total Environment, 2024)

RETRACTED: Hydrogen role in energy transition: A comparative review - Qusay Hassan; Sameer Algburi; Marek Jaszczur; Ali Khudhair Al-Jiboory; Tariq J. Al Musawi; Bashar Mahmood Ali; Patrik Viktor; Monika Fodor; Muhammad Ahsan; Hayder M. Salman; Aws Zuhair Sameen (Process Safety and Environmental Protection, 2024)

Assessing the impact of geopolitical, economic, and institutional factors on China's environmental management in the Russian-Ukraine conflicting era - Bilal Ahmed; Salman Wahab; Syed Rahim; Muhammad Imran; Afaq Ahmad Khan; Mohammed Moosa Ageli (Journal of Environmental Management, 2024)

Retraction Note: Asymmetric effect of FDI and public expenditure on population health: new evidence from Pakistan based on non-linear ARDL - Saif ur Rahman; Imran Sharif Chaudhry; Muhammad Saeed Meo; Salman Maqsood Sheikh; Sadia Idrees (Environmental Science and Pollution Research, 2024)

Identification and molecular mapping of a major gene conferring resistance to Phytophthora sansomeana in soybean ‘Colfax’ - Feng Lin; Muhammad Salman; Zhanguo Zhang; Austin G. McCoy; Wenlong Li; Raju Thada Magar; Drew Mitchell; Meixia Zhao; Cuihua Gu; Martin I. Chilvers; Dechun Wang (Theoretical and Applied Genetics, 2024)

Impact of meteorological parameters on aerosol optical depth and particulate matter in Lahore - Zahid Ur Rehman; Salman Tariq; Zia ul Haq; Muhammad Khan (Acta Geophysica, 2024)

Understanding catalytic hydrotreating of hydrothermal liquefaction nitrogen-rich biocrude in a two-stage continuous hydrotreater - Daniele Castello; Muhammad Salman Haider; Stefano Chiaberge; Lasse Aistrup Rosendahl (Chemical Engineering Journal, 2024)

Assessment of nighttime air quality over an urban location in Indo-Gangetic plain using remote sensing observations - Abd Alwahed Dagestani; Salman Tariq; Muhammad Khan; Mustafa Kamal; Masood ur Rehman (Atmospheric Pollution Research, 2024)

Retraction Note: Ameliorative effect of two structurally divergent hydrazide derivatives against DSS-induced colitis by targeting Nrf2 and NF-κB signaling in mice - Ashrafullah Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Sajjad Ahmad; Muhammad Usman Amin; Muhammad Naeem Ahmed; Zia‑ur‑Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Genome-wide association study reveals novel genes on different chromosomal positions regulating boll weight in upland cotton (Gossypium hirsutum L.) - Zubair Iqbal; Muhammad Shahid Iqbal; Salman Alamery; Khurram Shehzad; Qamar U. Zaman; Safira Attacha; Zareen Sarfraz; Mian Faisal Nazir; Daowu Hu; Muhammad Mubashar Zafar; Aqib Zeb; Shoupuhe; et al. (Genetic Resources and Crop Evolution, 2024)

An investigation of nighttime variability in air quality of Naples (Italy) using wavelet coherence - Salman Tariq; Muhammad Khan (Air Quality, Atmosphere & Health, 2024)

The impact of National Environmental Policy on Pakistan’s green economic development: evidence from regression discontinuity design - Muhammad Salman; Guimei Wang (Environment, Development and Sustainability, 2024)

Navigating environmental concerns: Unveiling the role of economic growth, trade, resources and institutional quality on greenhouse gas emissions in OECD countries - Salman Wahab; Muhammad Imran; Bilal Ahmed; Syed Rahim; Taimoor Hassan (Journal of Cleaner Production, 2024)

Patterns of bacterial communities in the rhizosphere and rhizoplane of alpine wet meadows - Awais Iqbal; Muhammad Maqsood Ur Rehman; Wasim Sajjad; Abraham Allan Degen; Muhammad Rafiq; Niu Jiahuan; Salman Khan; Zhanhuan Shang (Environmental Research, 2024)

Retraction Note: A new cationic palladium(II) dithiocarbamate exhibits anti-inflammatory, analgesic, and antipyretic activities through inhibition of inflammatory mediators in in vivo models - Muhammad Naveed; Shahan Zeb Khan; Sara Zeeshan; Adnan Khan; Bushra Shal; Ayesha Atiq; Hussain Ali; Rahim Ullah; Zia-ur-Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

RETRACTED: Bio-mitigation of organic pollutants using horseradish peroxidase as a promising biocatalytic platform for environmental sustainability - Muhammad Bilal; Anil Kumar Singh; Hafiz M.N. Iqbal; Tak H. Kim; Grzegorz Boczkaj; Khawlah Athmaneh; Syed Salman Ashraf (Environmental Research, 2023)

Evaluation of aquifer parameters through integrated approach of geophysical investigations, pumping test analysis and Dar-Zarrouk parameters in the central part of Bari Doab, Punjab, Pakistan - Shahbaz Muhammad; Perveiz Khalid; Muhammad Irfan Ehsan; Jahanzeb Qureshi; Salman Farooq (Environmental Monitoring and Assessment, 2023)

Reliability analysis of 15MW horizontal axis wind turbine rotor blades using fluid-structure interaction simulation and adaptive kriging model - Arvind Keprate; Nikhil Bagalkot; Muhammad Salman Siddiqui; Subhamoy Sen (Ocean Engineering, 2023)

Tackling microplastics pollution in global environment through integration of applied technology, policy instruments, and legislation - Tonni Agustiono Kurniawan; Ahtisham Haider; Ayesha Mohyuddin; Rida Fatima; Muhammad Salman; Anila Shaheen; Hafiz Muhammad Ahmad; Hussein E. Al-Hazmi; Mohd Hafiz Dzarfan Othman; Faissal Aziz; Abdelkader Anouzla; Imran Ali (Journal of Environmental Management, 2023)

A contemplating review on different synthesis methods of 2D-Molybdenum disulfide (MoS2) nanosheets - Syed Shujaat Karim; Abubakar Sudais; Muhammad Salman Shah; Sarah Farrukh; Subhan Ali; Mubashir Ahmed; Zarrar Salahuddin; Xianfeng Fan (Fuel, 2023)

Retraction Note: Inhibition of NF-κB signaling and HSP70/HSP90 proteins by newly synthesized hydrazide derivatives in arthritis model - Ashraf Ullah Khan; Amna Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Muhammad Naeem Ahmed; Salman Ul Islam; Hussain Ali; Adeeb Shehzad; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Investigating the effects of matrix acidizing and acid fracturing on the production optimization of a carbonate reservoir: a case study - Umair Qureshi; Haris Ahmed Qureshi; Amanat Ali Bhatti; Muhammad Salman Saeed; Muhammad Sameer Khalid (Arabian Journal of Geosciences, 2023)

An integrated approach for the extraction of lipids from marine macroalgae consortium using RSM optimization and thermo-kinetic analysis - Hamad AlMohamadi; Majed Alamoudi; Muhammad Zubair Yameen; Salman Raza Naqvi (Chemosphere, 2023)

Assessment of thermokinetic behaviour of tannery sludge in slow pyrolysis process through artificial neural network - Arslan Khan; Imtiaz Ali; Salman Raza Naqvi; Hamad AlMohamadi; Muhammad Shahbaz; Arshid Mahmood Ali; Khurram Shahzad (Chemosphere, 2023)

Automotive sustainable diesel blendstock production through biocrude obtained from hydrothermal liquefaction of municipal solid waste - Komeil Kohansal; Eliana Lozano Sanchez; Shivang Khare; Karl Oskar Pires Bjørgen; Muhammad Salman Haider; Daniele Castello; Terese Løvås; Lasse Aistrup Rosendahl; Thomas Helmer Pedersen (Fuel, 2023)

Fabrication of a novel nanocomposite (TiO2/WO3/V2O5) by hydrothermal method as catalyst for hazardous waste treatment - Umer Younas; Awais Ahmad; Aftab Islam; Faisal Ali; Muhammad Pervaiz; Aimon Saleem; Muhammad Waseem; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Salman Raza Naqvi (Fuel, 2023)

Simultaneous adsorption of methylene blue and amoxicillin by starch-impregnated MgAl layered double hydroxide: Parametric optimization, isothermal studies and thermo-kinetic analysis - Ghulam Mujtaba; Asad Ullah; Danish Khattak; Mansoor Ul Hassan Shah; Muhammad Daud; Salman Ahmad; Abdul Hai; Faheem Ahmed; Thamraa Alshahrani; Fawzi Banat (Environmental Research, 2023)

Ecological monitoring of urban thermal field variance index and determining the surface urban heat island effects in Lahore, Pakistan - Muhammad Nasar-u-Minallah; Dagmar Haase; Salman Qureshi; Sahar Zia; Munazza Fatima (Environmental Monitoring and Assessment, 2023)

Design and Evaluation of Continentalic Acid Encapsulated Transfersomal Gel and Profiling of its Anti-arthritis Activity - Muhammad Waseem Akram; Danish Mazhar; Iqra Afzal; Ahmad Zeb; Qurat Ul Ain; Salman Khan; Hussain Ali (AAPS PharmSciTech, 2023)

Correction to: Long-term spatio-temporal trends in atmospheric aerosols and trace gases over Pakistan using remote sensing - Muhammad Adil Javed; Usman Mehmood; Salman Tariq; Zia ul Haq (Acta Geophysica, 2023)

Catalytic pyrolysis of rice husk over defect-rich beta zeolites for biofuel production - Ali Azfar Zaidi; Arslan Khan; Hamad AlMohamadi; Muhammad Waqas Anjum; Imtiaz Ali; Salman Raza Naqvi; Shinya Kokuryo; Koji Miyake; Norikazu Nishiyama (Fuel, 2023)

Techno-economic assessment of sunflower husk pellets treated with waste glycerol for the Bio-Hydrogen production– A Simulation-based case study - Bilal Kazmi; Syed Ali Ammar Taqvi; Salman Raza Naqvi; Asif Ali Mirani; Muhammad Shahbaz; Muhammad Naqvi; Dagmar Juchelková; Gaber E. Eldesoky (Fuel, 2023)

Synthesis, chracterization, and analytical application of silver dopamine magnetic nanomaterial - Rahat Nawaz; Zarayb Hussan; Fahad Ali; Naeem Akhtar; Batool Fatima; Muhammad Najam ul Haq; Awais Bokhari; Salman Raza Naqvi; Mohamed Ouladsmane; Saadat Majeed (Fuel, 2023)

The impacts of heterogeneous environmental regulations on green economic efficiency from the perspective of urbanization: a dynamic threshold analysis - Guimei Wang; Muhammad Salman (Environment, Development and Sustainability, 2023)

Understanding the spatial spillover effect of land finance on China’s green development: does the moderating role of industrial structure matter? - Guimei Wang; Muhammad Salman (Environmental Science and Pollution Research, 2023)

Green financing strategy for low-carbon economy: The role of high-technology imports and institutional strengths in China - Taimoor Hassan; Yasir Khan; Adnan Safi; He Chaolin; Salman Wahab; Abdul Daud; Muhammad Tufail (Journal of Cleaner Production, 2023)

Metabolite fingerprinting of the ripening process in Pixian douban using a feature-based molecular network and metabolomics analysis - Weili Li; Sen Mei; Huanzhen Zhou; Muhammad Salman Farid; Tao Hu; Tao Wu (Food Chemistry, 2023)

Daidzein attenuated paclitaxel-induced neuropathic pain via the down-regulation of TRPV1/P2Y and up-regulation of Nrf2/HO-1 signaling - Sana Zafar; Yong Luo; Li Zhang; Chang Hu Li; Adnan Khan; Muhammad Ibrar Khan; Kifayatullah Shah; Eun Kyoung Seo; Feng Wang; Salman Khan (Inflammopharmacology, 2023)

Long-term spatio-temporal trends in atmospheric aerosols and trace gases over Pakistan using remote sensing - Muhammad Adil Javed; Usman Mehmood; Salman Tariq; Zia ul Haq (Acta Geophysica, 2023)

Economic and non-economic drivers of tourism: bidirectional causality of tourism and environment for South Asian economies - Salman Wahab; Bilal Ahmed; Muhammad Imran; Adnan Safi; Zeeshan Wahab (Environmental Science and Pollution Research, 2023)

Aspen plus simulation model of municipal solid waste gasification of metropolitan city for syngas production - Muzaffar Mehdi; Syed Ali Ammar Taqvi; Asif Ahmed Shaikh; Saad Khan; Salman Raza Naqvi; Muhammad Shahbaz; Dagmar Juchelková (Fuel, 2023)

Seismic risk assessment and hotspots prioritization: a developing country perspective - Rehan Asad; Muhammad Qaiser Saleem; Muhammad Salman Habib; Nadeem Ahmad Mufti; Shaker Mahmood Mayo (Natural Hazards, 2023)

Geotechnical properties of problematic expansive subgrade stabilized with guar gum biopolymer - Muhammad Hamza; Zhihong Nie; Mubashir Aziz; Nauman Ijaz; Chuanfeng Fang; Muhammad Usman Ghani; Zain Ijaz; Sadaf Noshin; Muhammad Salman (Clean Technologies and Environmental Policy, 2023)

Development of high-capacity surface-engineered MXene composite for heavy metal Cr (VI) removal from industrial wastewater - Umair Ali Asif; Khalid Mahmood; Salman Raza Naqvi; Muhammad Taqi Mehran; Tayyaba Noor (Chemosphere, 2023)

Endophytic bacterial diversity by 16S rRNA gene sequencing of Pak choi roots under fluazinam, Trichoderma harzianum, and Sophora flavescens inoculation - Shazma Gulzar; Muhammad Aamir Manzoor; Fiza Liaquat; Muhammad Salman Zahid; Samiah Arif; Xuanwei Zhou; Yidong Zhang (Functional & Integrative Genomics, 2023)

An ultrasensitive colorimetric and fluorescent “turn-on” chemosensor based on Schiff base for the detection of Cu2+ in the aqueous medium - Sikandar Khan; Mian Muhammad; Abdul Waheed Kamran; Hamed M. Al-Saidi; Salman S. Alharthi; Jari S. Algethami (Environmental Monitoring and Assessment, 2023)

In-field deployable and facile nanosensor for the detection of pesticides residues - Naveed Akhtar Shad; Anam Munawar; Yasir Javed; Allah Rakha; Ahsan Riaz; Salah Ud Din; Iqra Zareef; Muhammad Munir Sajid; Muahmmad Farhan Khan; Sareen Akhtar; Midhat Salman (Analytica Chimica Acta, 2023)

Mineralogy and PGE geochemistry of chromitites and peridotites of the sapat complex in the indus suture zone, northern Pakistan: implications for magmatic processes in the supra-subduction zone - Zaheen Ullah; Huan Li; Asad Khan; Shah Faisal; Yildirim Dilek; Michael W. Förster; Muhammad Farhan; Umar Ashraf; Salman Ahmed Khattak; Gohar Rehman; Syed Asim Hussain (International Geology Review, 2023)

Influence of Co3O4-based catalysts on N2O catalytic decomposition and NO conversion - Abrar Inayat; Lisandra Rocha-Meneses; Muhammad Ayoub; Sami Ullah; Ahmad Z. Abdullah; Salman R. Naqvi; Aamir H. Bhat (Environmental Science and Pollution Research, 2023)

Withametelin, a steroidal lactone, isolated from datura innoxa attenuates STZ-induced diabetic neuropathic pain in rats through inhibition of NF-kB/MAPK signaling - Adnan Khan; Bushra Shal; Ashraf Ullah Khan; Muhammad Waleed Baig; Ihsan ul Haq; Salman Khan (Food and Chemical Toxicology, 2023)

Risk assessment of circular economy practices in construction industry of Pakistan - Muhammad Salman Hassan; Yousaf Ali; Antonella Petrillo; Fabio De Felice (Science of The Total Environment, 2023)

Stimulants and donors promote megaplasmid pND6-2 horizontal gene transfer in activated sludge - Shan Wang; Shanshan Li; Dan Du; Olusegun K. Abass; Muhammad Salman Nasir; Wei Yan (Journal of Environmental Sciences, 2023)

A systematic and critical review on effective utilization of artificial intelligence for bio-diesel production techniques - Junaid Ahmad; Muhammad Awais; Umer Rashid; Chawalit Ngamcharussrivichai; Salman Raza Naqvi; Imtiaz Ali (Fuel, 2023)

Advances in production & activation of marine macroalgae-derived biochar catalyst for sustainable biodiesel production - Muhammad Zubair Yameen; Hamad AlMohamadi; Salman Raza Naqvi; Tayyaba Noor; Wei-Hsin Chen; Nor Aishah Saidina Amin (Fuel, 2023)

LC-ESI-QTOF-MS/MS profiling of phenolic compounds in Australian native plums and their potential antioxidant activities - Jiaxun Li; Haoyao Liu; Muhammad Sohail Mazhar; Salman Quddus; Hafiz Ansar Rasul Suleria (Food Bioscience, 2023)

Piezocatalytic removal of water bacteria and organic compounds: a review - Ahsan Ali; Longbin Chen; Muhammad Salman Nasir; Chao Wu; Baolin Guo; Yaodong Yang (Environmental Chemistry Letters, 2023)

Micromorphological characterization of seeds of dicot angiosperms from the Thal desert (Pakistan) - Salman Majeed; Mushtaq Ahmad; Fethi Ahmet Ozdemir; Azize Demirpolat; Zeynep Şahan; Trobjon Makhkamov; Muhtor Nasirov; Muhammad Zafar; Shazia Sultana; Ghulam Yaseen; Nabila (Plant Biosystems, 2023)

Metal organic frameworks as promising sensing tools for electrochemical detection of persistent heavy metal ions from water matrices: A concise review - Syed Salman Shafqat; Muhammad Rizwan; Maria Batool; Syed Rizwan Shafqat; Ghulam Mustafa; Tahir Rasheed; Muhammad Nadeem Zafar (Chemosphere, 2023)

Removal of ceftriaxone sodium antibiotic from pharmaceutical wastewater using an activated carbon based TiO2 composite: Adsorption and photocatalytic degradation evaluation - Muneeb Abdullah; Javed Iqbal; Muhammad Saif Ur Rehman; Usman Khalid; Fahad Mateen; Salman Noshear Arshad; Abdullah G. Al-Sehemi; Hamed Algarni; Omar A. Al-Hartomy; Tahir Fazal (Chemosphere, 2023)

The driving influence of multidimensional urbanization on green total factor productivity in China: evidence from spatiotemporal analysis - Guimei Wang; Muhammad Salman (Environmental Science and Pollution Research, 2023)

Variations in the aerosol index and its relationship with meteorological parameters over Pakistan using remote sensing - Muhammad Khan; Salman Tariq; Zia Ul Haq (Environmental Science and Pollution Research, 2023)

Understanding the demetallization of nitrogen-rich hydrothermal liquefaction biocrudes by FTICR mass spectrometry: Recalcitrant effect of metalloporphyrins and basic nitrogenates - Muhammad Salman Haider; Stefano Chiaberge; Andrea Siviero; Mehmed Akif Isik; Daniele Castello; Thomas Helmer Pedersen; Lasse Aistrup Rosendahl (Fuel, 2023)

Recent progress in catalytic deoxygenation of biomass pyrolysis oil using microporous zeolites for green fuels production - Salman Raza Naqvi; Asif Hussain Khoja; Imtiaz Ali; Muhammad Naqvi; Tayyaba Noor; Awais Ahmad; Rafael Luque; Nor Aishah Saidina Amin (Fuel, 2023)

Biocatalytic degradation of reactive blue 221 and direct blue 297 dyes by horseradish peroxidase immobilized on iron oxide nanoparticles with improved kinetic and thermodynamic characteristics - Umme Kalsoom; Nasira Khalid; Affaf Ibrahim; Syed Salman Ashraf; Haq Nawaz Bhatti; Zainab Ahsan; Jakub Zdarta; Muhammad Bilal (Chemosphere, 2023)

Polygeneration syngas and power from date palm waste steam gasification through an Aspen Plus process modeling - Arshid Mahmood Ali; Muhammad Shahbaz; Khurram Shahzad; Muddasser Inayat; Salman Naqvi; Abdulrahim Ahmad Al-Zahrani; Muhammad Imtiaz Rashid; Mohammad Rehan; Aishah Binti Mahpudz (Fuel, 2023)

Applications of machine learning in thermochemical conversion of biomass-A review - Muzammil khan; Salman Raza Naqvi; Zahid Ullah; Syed Ali Ammar Taqvi; Muhammad Nouman Aslam Khan; Wasif Farooq; Muhammad Taqi Mehran; Dagmar Juchelková; Libor Štěpanec (Fuel, 2023)

Correction to: The estimation of influencing factors for carbon emissions based on EKC hypothesis and STIRPAT model: Evidence from top 10 countries - Ellen Thio; MeiXuen Tan; Liang Li; Muhammad Salman; Xingle Long; Huaping Sun; Bangzhu Zhu (Environment, Development and Sustainability, 2023)

Metal–Organic Framework-Based Composites for the Detection and Monitoring of Pharmaceutical Compounds in Biological and Environmental Matrices - Muhammad Rizwan; Vidhya Selvanathan; Atta Rasool; Muhammad Anees ur Rehman Qureshi; Dure Najaf Iqbal; Qudsia Kanwal; Syed Salman Shafqat; Tahir Rasheed; Muhammad Bilal (Water, Air, & Soil Pollution, 2022)

Sedimentological and diagenetic analysis of Early Eocene Margalla Hill Limestone, Shahdara area, Islamabad, Pakistan: implications for reservoir potential - Haroon Aziz; Jabir Hussain; Muhammad Tariq; Muhsan Ehsan; Salman Khurshid; Saleem Khan; Waleed Anwar (Carbonates and Evaporites, 2022)

Assessing the impact of green consumption behavior and green purchase intention among millennials toward sustainable environment - Madad Ali; Shakir Ullah; Muhammad Salman Ahmad; Mui Yee Cheok; Hamood Alenezi (Environmental Science and Pollution Research, 2022)

Tanneries impact on groundwater quality: a case study of Kasur city in Pakistan - Hafiz Qasim Ali; Muhammad Umair Yasir; Amir Farooq; Mahrukh Khan; Muhammad Salman; Muhammad Waqar (Environmental Monitoring and Assessment, 2022)

RETRACTED ARTICLE: Ameliorative effect of two structurally divergent hydrazide derivatives against DSS-induced colitis by targeting Nrf2 and NF-κB signaling in mice - Ashrafullah Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Sajjad Ahmad; Muhammad Usman Amin; Muhammad Naeem Ahmed; Zia-ur-Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

A static and dynamic copula-based ARIMA-fGARCH approach to determinants of carbon dioxide emissions in Argentina - Sel Ly; Salman Sarwat; Wing-Keung Wong; Muhammad Ramzan; Hung D. Nguyen (Environmental Science and Pollution Research, 2022)

Spatial green growth in China: exploring the positive role of investment in the treatment of industrial pollution - Muhammad Imran; Naveed Hayat; Muhammad Ali Saeed; Abdul Sattar; Salman Wahab (Environmental Science and Pollution Research, 2022)

Comparative Transcriptomic and Metabolomic Profiling of Grapevine Leaves (cv. Kyoho) upon Infestation of Grasshopper and Botrytis cinerea - Haoran Jia; Teng Li; Muhammad Salman Haider; Ehsan Sadeghnezhad; Qianqian Pang; Jian Han; Peian Zhang; Lingyun Su; Haifeng Jia; Jinggui Fang (Plant Molecular Biology Reporter, 2022)

Structural and Electronic (Absorption and Fluorescence) Properties of a Stable Triplet Diphenylcarbene: A DFT Study - Abrar Ul Hassan; Ayesha Mohyuddin; Sohail Nadeem; Cihat Güleryüz; Sadaf Ul Hassan; Mohsin Javed; Muhammad Salman Muhsan (Journal of Fluorescence, 2022)

Heterogeneous environmental regulations and green economic efficiency in China: the mediating role of industrial structure - Guimei Wang; Kaiming Cheng; Yusen Luo; Muhammad Salman (Environmental Science and Pollution Research, 2022)

The estimation of influencing factors for carbon emissions based on EKC hypothesis and STIRPAT model: Evidence from top 10 countries - Ellen Thio; MeiXuen Tan; Liang Li; Muhammad Salman; Xingle Long; Huaping Sun; Bangzhu Zhu (Environment, Development and Sustainability, 2022)

Palynological Diversity of Melliferous flora around Apiaries from District Mardan Khyber Pakhtunkhwa-Pakistan - Nabila; Mushtaq Ahmad; Muhammad Ali; Muhammad Zafar; Shazia Sultana; Salman Majeed; Ghulam Yaseen; Shabir Ahmad (The Botanical Review, 2022)

Antileishmanial Agents Co-loaded in Transfersomes with Enhanced Macrophage Uptake and Reduced Toxicity - Fatima Zahid; Sibgha Batool; Fakhar ud-Din; Zakir Ali; Muhammad Nabi; Salman Khan; Omer Salman; Gul Majid Khan (AAPS PharmSciTech, 2022)

Systematic significance of seed morphology and foliar anatomy among Acanthaceous taxa - Jamil Raza; Mushtaq Ahmad; Muhammad Zafar; Ghulam Yaseen; Shazia Sultana; Salman Majeed (Biologia, 2022)

Protection against reinforcement corrosion using various hydroxy acid-based rust converters: tests in mortar medium - Muhammad Salman; Muhammad Ali Sikandar; Hassan Nasir; Muhammad Waseem; Shahid Iqbal (European Journal of Environmental and Civil Engineering, 2022)

Role of financial stability, technological innovation, and renewable energy in achieving sustainable development goals in BRICS countries - Salman Wahab; Muhammad Imran; Adnan Safi; Zeeshan Wahab; Dervis Kirikkaleli (Environmental Science and Pollution Research, 2022)

Integrating green business strategies and green competencies to enhance green innovation: evidence from manufacturing firms of Pakistan - Salman Yahya; Adnan Khan; Maryam Farooq; Muhammad Irfan (Environmental Science and Pollution Research, 2022)

Variations in the Serum Sialic Acid Profiles of Malaria Patients in Zaria, Nigeria: A Cross-Sectional Study - Mbateudi Danjuma Ika; Mohammed Auwal Ibrahim; Abdullahi Balarabe Sallau; Abdulmalik Abdullahi Salman; Abubakar Muhammad Sani; Murtala Bindawa Isah (Acta Parasitologica, 2022)

Environmental concerns of financial inclusion and economic policy uncertainty in the era of globalization: evidence from low & high globalized OECD economies - Sami Ullah; Kishwar Ali; Salman Ali Shah; Muhammad Ehsan (Environmental Science and Pollution Research, 2022)

Cyclo(L-Leucyl-L-Prolyl) from Lactobacillus coryniformis BCH-4 inhibits the proliferation of Aspergillus flavus: an in vitro to in silico approach - Mahwish Salman; Anam Tariq; Ghulam Mustafa; Muhammad Rizwan Javed; Shazia Naheed; Sarmad Ahmad Qamar (Archives of Microbiology, 2022)

Response of urban tree DBH to fast urbanization: Case of coastal Zhanjiang in south China - Xia-Lan Cheng; Mir Muhammad Nizamani; Chi-Yung Jim; Salman Qureshi; Shuang Liu; Zhi-Xin Zhu; Si-Si Wu; Kelly Balfour; Hua-Feng Wang (Urban Ecosystems, 2022)

Biosurfactants and chemotaxis interplay in microbial consortium-based hydrocarbons degradation - Muhammad Ibrar; Salman Khan; Fariha Hasan; Xuewei Yang (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Asymmetric effect of FDI and public expenditure on population health: new evidence from Pakistan based on non-linear ARDL - Saif ur Rahman; Imran Sharif Chaudhry; Muhammad Saeed Meo; Salman Maqsood Sheikh; Sadia Idrees (Environmental Science and Pollution Research, 2022)

Malignancy risk in individuals with familial adenomatous polyposis receiving biologics and immunomodulators - Muhammad Salman Faisal; Carol A. Burke; Jean-Paul Achkar; Benjamin Click; Margaret O’Malley; Lisa LaGuardia; Susan Milicia; Brandie Leach; David Liska; James Church; Matthew Kalady; Gautam Mankaney (Familial Cancer, 2022)

Do environmental pollutants carrier to COVID-19 pandemic? A cross-sectional analysis - Salman Shamsi; Khalid Zaman; Bushra Usman; Abdelmohsen A. Nassani; Mohamed Haffar; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2022)

Functionalized multi-walled carbon nanotubes for oil spill cleanup from water - Thamer Adnan Abdullah; Tatjana Juzsakova; Sanaa A. Hafad; Rashed Taleb Rasheed; Noor Al-Jammal; Muhammad Ali Mallah; Ali Dawood Salman; P. C. Le; Endre Domokos; Mustafa Aldulaimi (Clean Technologies and Environmental Policy, 2022)
The growing global economy resulted in an incessant increase in transportation and exploitation of oil. Hence, the oil spillage has been considered a serious threat to aquatic and terrestrial ecosystems. Therefore, water purification has been considered a major challenge around the world. There are numerous classical methods available for oil removal from water, but owing to multiple defects and disadvantages, research efforts have focused to find such adsorbents which can improve oil adsorption capability. Traditional adsorbent material typically applied in oil removal includes activated carbon, organoclays, wool, zeolites, etc. These materials suffer from several drawbacks such as low absorption capacity, non-selective absorption, and complicated reusability, whereas nano-adsorbents offer multiple advantages such as having multiple sorption sites, large surface area, short intra-particle diffusion distance, tuneable pore size, and ease of low-temperature modification. Multi-walled carbon nanotubes (MWCNTs) are extensively used adsorbent materials with a strong affinity for the removal of organic pollutants. The functionalization MWCNTs further increase the sorption capacity of adsorbents manifolds to remove organic materials. These nanocomposites are also compatible with green materials and considered environmentally friendly adsorbents. This review paper aims at providing an insight to understand the properties of the MWCNTs and their potential use to adsorb hydrocarbons from water. Moreover, the synthesis methods of those materials, their modification procedures including the functionalization with metal oxide nanoparticles, and applications are also discussed in detail. Graphic abstract

Muricazine, a new hydrazine derivative from Ranunculus muricatus L. with antioxidant, lipoxygenase and urease inhibitory activities - Naila Raziq; Muhammad Saeed; Muhammad Shaiq Ali; Muhammad Shahid; Mehreen Lateef; Salman Zafar (Natural Product Research, 2022)

Higher hydrogen production by photocatalytic water splitting using a hollow tubular graphitic carbon nitride-zinc telluride composite - Muhammad Salman Nasir; Guorui Yang; Iqra Ayub; Abdul Nasir; Wei Yan (Environmental Chemistry Letters, 2022)

Muriolide, a novel antioxidant lactone from Ranunculus muricatus - Naila Raziq; Muhammad Saeed; Muhammad Shaiq Ali; Mehreen Lateef; Muhammad Shahid; Shehla Akbar; Salman Zafar (Natural Product Research, 2021)

Anti-neuropathic pain activity of a cationic palladium (II) dithiocarbamate by suppressing the inflammatory mediators in paclitaxel-induced neuropathic pain model - Muhammad Naveed; Rahim Ullah; Adnan Khan; Bushra Shal; Ashraf Ullah Khan; Shahan Zeb Khan; Zia ur Rehman; Salman Khan (Molecular Biology Reports, 2021)

Assessing the potential of partial root zone drying and mulching for improving the productivity of cotton under arid climate - Rashid Iqbal; Muhammad Habib-ur-Rahman; Muhammad Aown Sammar Raza; Muhammad Waqas; Rao Muhammad Ikram; Muhammad Zeshan Ahmed; Monika Toleikiene; Muhammad Ayaz; Farhan Mustafa; Salman Ahmad; Muhammad Usman Aslam; Muhammad Mohsin Waqas; et al. (Environmental Science and Pollution Research, 2021)
Water scarcity constrains global cotton production. However, partial root-zone drying (PRD) and mulching can be used as good techniques to save water and enhance crop production, especially in arid regions. This study aimed to evaluate the effects of mulching for water conservation in an arid environment under PRD and to further assess the osmotic adjustment and enzymatic activities for sustainable cotton production. The study was carried out for 2 years in field conditions using mulches (NM = no mulch, BPM = black plastic mulch at 32 kg ha -1 , WSM = wheat straw mulch at 3 tons ha -1 , CSM = cotton sticks mulch at 10 tons ha -1 ) and two irrigation levels (FI = full irrigation and PRD (50% less water than FI). High seed cotton yield (SCY) achieved in FI+WSM (4457 and 4248 kg ha -1 in 2017 and 2018, respectively) and even in PRD+WSM followed by BPM>CSM>NM under FI and PRD for both years. The higher SCY and traits observed in FI+WSM and PRD+WSM compared with the others were attributed to the improved water use efficiency and gaseous exchange traits, increased hormone production (ABA), osmolyte accumulation, and enhanced antioxidants to scavenge the excess reactive oxygen. Furthermore, better cotton quality traits were also observed under WSM either with FI or PRD irrigation regimes. Mulches applications found effective to control the weeds in the order as BPM>WSM>CSM. In general, PRD can be used as an effective stratagem to save moisture along with WSM, which ultimately can improve cotton yield in the water-scarce regions under arid climatic regions. It may prove as a good adaptation strategy under current and future water shortage scenarios of climate change.

Arsenic exposure through drinking groundwater and consuming wastewater-irrigated vegetables in Multan, Pakistan - Mamoona Amir; Salman Asghar; Muhammad Ahsin; Shahid Hussain; Amir Ismail; Muhammad Riaz; Safina Naz (Environmental Geochemistry and Health, 2021)

Light-off Investigation of Oxymethylene Ether (OME) Considering the Presence of the Exhaust Components Heptane, Carbon, and Nitrogen Monoxide - Florian Rümmele; Alexander Susdorf; Syed Muhammad Salman Haider; Robert Szolak (Emission Control Science and Technology, 2021)
Synthetic fuels and fuel blends like OMEs can contribute to tank-to-wheel CO 2 emission savings. At the same time, it is known that these fuels have a lower exhaust temperature compared to conventional diesel. This effect has major impact on the exhaust after-treatment system, particularly in cold start conditions. This paper investigates the light-off behavior of exhaust gases containing OMEs by temperature-programmed oxidation experiments using a state-of-the-art oxidation catalyst. The main side product of catalytic oxidation of OMEs between 100 °C and the oxidation temperature T 50 , which was around 160 °C, was shown to be formaldehyde. While alkane oxidation, in this case heptane, was little influenced by OME oxidation, the oxidation temperature T 50 of CO increases by more than 10 °C by OME addition. Nitrogen monoxide impeded the oxidation of OME in a similar way to the other components investigated. Due to the amount of FA produced and its toxicity, it could be concluded that it is necessary to heat up exhaust after-treatment systems of OME diesel engines even faster than conventional diesel exhaust after-treatment systems. The relatively high reactivity of OME on oxidation catalyst can be used by active thermal management approaches.

Systematic investigation of Iranian Vacuum Bottom hydrodenitrogenation to produce clean fuel oil for marine transportation - Mohammad Salimi; Havva Hashemi; Muhammad Salman Haider; Lasse Aistrup Rosendahl (Energy, Ecology and Environment, 2021)

RETRACTED ARTICLE: COVID-19 and stock exchange return variation: empirical evidences from econometric estimation - Yousaf Latif; Ge Shunqi; Shahid Bashir; Wasim Iqbal; Salman Ali; Muhammad Ramzan (Environmental Science and Pollution Research, 2021)

Distinct genetic landscape and a low response to doxorubicin in a luminal-A breast cancer cell line of Pakistani origin - Muhammad Shakeel; Salman Ahmed Khan; Anum Jabeen Mughal; Muhammad Irfan; Daniel C. Hoessli; M. Iqbal Choudhary; Muhammad Aurongzeb; Ishtiaq Ahmad Khan (Molecular Biology Reports, 2021)

Melatonin-Induced Salinity Tolerance by Ameliorating Osmotic and Oxidative Stress in the Seedlings of Two Tomato (Solanum lycopersicum L.) Cultivars - Muhammad Ali; Muhammad Kamran; Ghulam Hassan Abbasi; Muhammad Hamzah Saleem; Salman Ahmad; Aasma Parveen; Zaffar Malik; Sobia Afzal; Sunny Ahmar; Khadim Muhammad Dawar; Sardar Ali; Saud Alamri; et al. (Journal of Plant Growth Regulation, 2021)

Silver nanoparticles biosynthesized from secondary metabolite producing marine actinobacteria and evaluation of their biomedical potential - Ashia Alam; Faouzia Tanveer; Ali Talha Khalil; Tanzeel Zohra; Saleh Khamlich; Muhammad Masroor Alam; Muhammad Salman; Muhammad Ali; Aamer Ikram; Zabta Khan Shinwari; Malik Maaza (Antonie van Leeuwenhoek, 2021)

Investigating the flood damages in Lower Indus Basin since 2000: Spatiotemporal analyses of the major flood events - Salman Atif; Muhammad Umar; Fahim Ullah (Natural Hazards, 2021)

Jasmonic acid: a key frontier in conferring abiotic stress tolerance in plants - Ali Raza; Sidra Charagh; Zainab Zahid; Muhammad Salman Mubarik; Rida Javed; Manzer H. Siddiqui; Mirza Hasanuzzaman (Plant Cell Reports, 2021)

Bioaccumulation of zinc in edible tropical vegetables in Peninsular Malaysia and its human health risk assessment based on various ethnicities in Malaysia - Koe Wei Wong; Chee Kong Yap; Aziran Yaacob; Rosimah Nulit; Hishamuddin Omar; Ahmad Zaharin Aris; Moslem Sharifinia; Alireza Riyahi Bakhtiari; Salman Abdo Al-Shami; Muhammad Saleem; Hideo Okamura (Environmental Science and Pollution Research, 2021)

HEC-RAS and GIS-based flood plain mapping: A case study of Narai Drain Peshawar - Awais Salman; Sher Shah Hassan; Gul Daraz Khan; Muhammad Arif Goheer; Aftab Ahmad Khan; Khurram Sheraz (Acta Geophysica, 2021)

RETRACTED ARTICLE: Inhibition of NF-κB signaling and HSP70/HSP90 proteins by newly synthesized hydrazide derivatives in arthritis model - Ashraf Ullah Khan; Amna Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Muhammad Naeem Ahmed; Salman Ul Islam; Hussain Ali; Adeeb Shehzad; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

The role of financial development indicators in sustainable development-environmental degradation nexus - Xiaolong Li; Zhiyuan Yu; Asma Salman; Qaisar Ali; Muhammad Hafeez; Muhammad Shoaib Aslam (Environmental Science and Pollution Research, 2021)

Growth and physio-biochemical responses of maize ( Zea mays L.) to drought and heat stresses - Madiha Ayub; Muhammad Yasin Ashraf; Abida Kausar; Salman Saleem; Sumera Anwar; Volkan Altay; Munir Ozturk (Plant Biosystems, 2021)

RETRACTED ARTICLE: The step towards environmental mitigation in Pakistan: do transportation services, urbanization, and financial development matter? - Danish Iqbal Godil; Paiman Ahmad; Muhammad Sajjad Ashraf; Salman Sarwat; Arshian Sharif; Syed Shabib-ul-Hasan; Kittisak Jermsittiparsert (Environmental Science and Pollution Research, 2021)

Elevated anxiety, hypoactivity, memory deficits, decreases of brain serotonin and 5-HT-1A receptors expression in rats treated with omeprazole - Sadia Basharat Ali; Khalid Mahmood; Raheel Saeed; Tabinda Salman; Muhammad Iqbal Choudhary; Darakhshan Jabeen Haleem (Toxicological Research, 2021)

Landfill site selection by integrating fuzzy logic, AHP, and WLC method based on multi-criteria decision analysis - Riaz Zarin; Muhammad Azmat; Salman Raza Naqvi; Qaisar Saddique; Saif Ullah (Environmental Science and Pollution Research, 2021)

The influence of technological innovation and human capital on environmental efficiency among different regions in Asia-Pacific - Florence Appiah Twum; Xingle Long; Muhammad Salman; Claudia Nyarko Mensah; William Adomako Kankam; Andrew Kwamena Tachie (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: Closed-loop supply chain network design with sustainability and resiliency criteria - Muhammad Salman Shabbir; Arshad Mahmood; Roy Setiawan; Chairun Nasirin; Rusdiyanto Rusdiyanto; Gazali Gazali; Mohd Anuar Arshad; Shahid Khan; Fatima Batool (Environmental Science and Pollution Research, 2021)

Biochar and leguminous cover crops as an alternative to summer fallowing for soil organic carbon and nutrient management in the wheat-maize-wheat cropping system under semiarid climate - Muhammad Arif; Ikramullah; Talha Jan; Muhammad Riaz; Kashif Akhtar; Salman Ali; Shahen Shah; Fazal Jalal; Ishaq A. Mian; Khadim Muhammad Dawar; Haiyan Wang (Journal of Soils and Sediments, 2021)

Does the modifying role of institutional quality remains homogeneous in GDP-CO2 emission nexus? New evidence from ARDL approach - Usman Mehmood; Salman Tariq; Zia Ul-Haq; Muhammad Saeed Meo (Environmental Science and Pollution Research, 2021)

One district one factory policy of Ghana, a transition to a low-carbon habitable economy? - Claudia Nyarko Mensah; Lamini Dauda; Kofi Baah Boamah; Muhammad Salman (Environment, Development and Sustainability, 2021)

Genome-wide analysis of glutathione S-transferase gene family in G. max - Muhammad Zulfiqar Ahmad; Jamal Abdul Nasir; Shakeel Ahmed; Bushra Ahmad; Aiman Sana; Said Salman; Zamarud Shah; CunYi Yang (Biologia, 2020)

Soil fungal taxonomic diversity along an elevation gradient on the semi-arid Xinglong Mountain, Northwest China - Salman Khan; Ning Chen; Cankun Zhang; Luning Wang; Chun Han; Kanglong Lu; Yage Li; Muhammad Rafiq; Awais Iqbal; Changming Zhao (Archives of Microbiology, 2020)

RETRACTED ARTICLE: Matrine alleviates neurobehavioral alterations via modulation of JNK-mediated caspase-3 and BDNF/VEGF signaling in a mouse model of burn injury - Adnan Khan; Bushra Shal; Muhammad Naveed; Bakht Nasir; Nadeem Irshad; Hussain Ali; Salman Khan (Psychopharmacology, 2020)

Assessment of antibiotics use for children upper respiratory tract infections: a retrospective, cross-sectional study from Pakistan - Zia Ul Mustafa; Muhammad Salman; Alina Zeeshan Rao; Noman Asif; Sanan Amjad Butt; Naureen Shehzadi; Khalid Hussain (Infectious Diseases, 2020)

Revisiting the cytotoxicity of quantum dots: an in-depth overview - Sohrab Nikazar; Vishnu Sankar Sivasankarapillai; Abbas Rahdar; Salim Gasmi; P S Anumol; Muhammad Salman Shanavas (Biophysical Reviews, 2020)

Characterization of antifungal metabolites produced by Lactobacillus plantarum and Lactobacillus coryniformis isolated from rice rinsed water - Shazia Anwer Bukhari; Mahwish Salman; Muhammad Numan; Muhammad Rizwan Javed; Muhammad Zubair; Ghulam Mustafa (Molecular Biology Reports, 2020)

Does regional energy consumption disparities assist to control environmental degradation in OBOR: an entropy approach - Guijuan Sun; Chunhui Yuan; Muhammad Hafeez; Salman Raza; Liu Jie; Xiaodan Liu (Environmental Science and Pollution Research, 2020)

Citric Acid Functionalized Bougainvillea spectabilis: a Novel, Sustainable, and Cost-effective Biosorbent for Removal of Heavy Metal (Pb2+) from Waste Water - Huma Nazir; Muhammad Salman; Makshoof Athar; Umar Farooq; Abdul Wahab; Momal Akram (Water, Air, & Soil Pollution, 2019)

Economics of death and dying: a critical evaluation of environmental damages and healthcare reforms across the globe - Rubeena Batool; Khalid Zaman; Muhammad Adnan Khurshid; Salman Masood Sheikh; Alamzeb Aamir; Alaa Mohamd Shoukry; Mohamed A. Sharkawy; Fares Aldeek; Jameel Khader; Showkat Gani (Environmental Science and Pollution Research, 2019)

RETRACTED ARTICLE: A new cationic palladium(II) dithiocarbamate exhibits anti-inflammatory, analgesic, and antipyretic activities through inhibition of inflammatory mediators in in vivo models - Muhammad Naveed; Shahan Zeb Khan; Sara Zeeshan; Adnan Khan; Bushra Shal; Ayesha Atiq; Hussain Ali; Rahim Ullah; Zia-ur-Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Hepatitis E outbreak in the province of Punjab, Pakistan: a call for action - Muhammad Salman; Zia Ul Mustafa; Noman Asif (Infectious Diseases, 2019)

An empirical evaluation of financial development-carbon footprint nexus in One Belt and Road region - Muhammad Hafeez; Chunhui Yuan; Khuram Shahzad; Babar Aziz; Kashif Iqbal; Salman Raza (Environmental Science and Pollution Research, 2019)

Innovation and CO2 emissions: the complimentary role of eco-patent and trademark in the OECD economies - Claudia Nyarko Mensah; Xingle Long; Lamini Dauda; Kofi Baah Boamah; Muhammad Salman (Environmental Science and Pollution Research, 2019)

Ultrasonic assisted improved extraction and dyeing of mordanted silk fabric using neem bark as source of natural colourant - Shahid Adeel; Khalid Mahmood Zia; Muhammad Abdullah; Fazal-ur- Rehman; Mahwish Salman; Mohammad Zuber (Natural Product Research, 2019)

N-Pyrazoloyl and N-thiopheneacetyl hydrazone of isatin exhibited potent anti-inflammatory and anti-nociceptive properties through suppression of NF-κB, MAPK and oxidative stress signaling in animal models of inflammation - Sara Zeeshan; Muhammad Naveed; Adnan Khan; Ayesha Atiq; Maryam Arif; Muhammad Naeem Ahmed; Yeong Shik Kim; Salman Khan (Inflammation Research, 2019)

Correction to: Ecological risk assessment of metals in sediments and selective plants of Uchalli Wetland Complex (UWC)—a Ramsar site - Sumera Gull Bhatti; Amtul Bari Tabinda; Faisal Yasin; Adeel Mehmood; Muhammad Salman; Abdullah Yasar; Rizwan Rasheed; Rabia Wajahat (Environmental Science and Pollution Research, 2019)

Recent advances in the application of silica nanostructures for highly improved water treatment: a review - Muhammad Salman; Shanaz Jahan; Shamsa Kanwal; Farrukh Mansoor (Environmental Science and Pollution Research, 2019)

Ecological risk assessment of metals in sediments and selective plants of Uchalli Wetland Complex (UWC)—a Ramsar site - Sumera Gull Bhatti; Amtul Bari Tabinda; Faisal Yasin; Adeel Mehmood; Muhammad Salman; Abdullah Yasar; Rizwan Rasheed; Rabia Wajahat (Environmental Science and Pollution Research, 2019)

Evidence of zoonotic transmission of VP6 and NSP4 genes into human species A rotaviruses isolated in Pakistan in 2010 - Sana Tamim; Jelle Matthijnssens; Elisabeth Heylen; Mark Zeller; Marc Van Ranst; Muhammad Salman; Fariha Hasan (Archives of Virology, 2019)

N2O, CH4, and CO2 Emissions from Continuous Flooded, Wet, and Flooded Converted to Wet Soils - Muhammad Salman Khalid; Muhammad Shaaban; Ronggui Hu (Journal of Soil Science and Plant Nutrition, 2019)

The effects of economic growth and innovation on CO2 emissions in different regions - Lamini Dauda; Xingle Long; Claudia Nyarko Mensah; Muhammad Salman (Environmental Science and Pollution Research, 2019)

Thermodynamic and kinetic insights into plant-mediated detoxification of lead, cadmium, and chromium from aqueous solutions by chemically modified Salvia moorcroftiana leaves - Syed Muhammad Salman; Asad Ali; Behramand Khan; Mehmood Iqbal; Muhammad Alamzeb (Environmental Science and Pollution Research, 2019)

Folate-Functionalized Thiomeric Nanoparticles for Enhanced Docetaxel Cytotoxicity and Improved Oral Bioavailability - Muhammad Sajjad; Muhammad Imran Khan; Sara Naveed; Sana Ijaz; Omer Salman Qureshi; Syed Atif Raza; Gul Shahnaz; Muhammad Farhan Sohail (AAPS PharmSciTech, 2019)

Characterization of Vv-miR156: Vv-SPL pairs involved in the modulation of grape berry development and ripening - Mengjie Cui; Chen Wang; Wenying Zhang; Tariq Pervaiz; Muhammad Salman Haider; Wei Tang; Jinggui Fang (Molecular Genetics and Genomics, 2018)

Life cycle assessment to evaluate the environmental performance of new construction material from stainless steel slag - Andrea Di Maria; Muhammad Salman; Maarten Dubois; Karel Van Acker (The International Journal of Life Cycle Assessment, 2018)

Gibberellins application timing modulates growth, physiology, and quality characteristics of two onion (Allium cepa L.) cultivars - Salman Mushtaq; Muhammad Amjad; Khurram Ziaf; Irfan Afzal (Environmental Science and Pollution Research, 2018)

Correction to: Anti-inflammatory, anti-rheumatic and analgesic activities of 2-(5-mercapto-1,3,4-oxadiazol-2-yl)-N-propylbenzenesulphonamide (MOPBS) in rodents - Hina Rasheed; Ruqayya Afridi; Ashraf Ullah Khan; Muhammad Zia Ullah; Sidra Khalid; Ayesha Atiq; Humaira Kashif; Muhammad Naeem Ahmed; Yeong Shik Kim; Salman Khan (Inflammopharmacology, 2018)

Anti-inflammatory, anti-rheumatic and analgesic activities of 2-(5-mercapto-1,3,4-oxadiazol-2-yl)-N-propylbenzenesulphonamide (MOPBS) in rodents - Hina Rasheed; Ruqayya Afridi; Ashraf Ullah Khan; Muhammad Zia Ullah; Sidra Khalid; Ayesha Atiq; Humaira Kashif; Muhammad Naeem Ahmed; Yeong Shik Kim; Salman Khan (Inflammopharmacology, 2018)

Correction to: Multi-sensor temporal assessment of tropospheric nitrogen dioxide column densities over Pakistan - Rabbia Murtaza; Muhammad Fahim Khokhar; Asma Noreen; Salman Atif; Khalid Rehman Hakeem (Environmental Science and Pollution Research, 2018)

Multi-sensor temporal assessment of tropospheric nitrogen dioxide column densities over Pakistan - Rabbia Murtaza; Muhammad Fahim Khokhar; Asma Noreen; Salman Atif; Khalid Rehman Hakeem (Environmental Science and Pollution Research, 2018)

Comparison of total ozone column observations from space-borne Ozone Monitoring Instrument with ground-based Dobson Ozone Spectrophotometer measurements at an urban location in Indo-Gangetic Basin - Zia Ul-Haq; Zertasha Ramzan; Salman Tariq; Syeda Adila Batool; Muhammad Ali; Javed Sami (International Journal of Remote Sensing, 2018)

Effect of a bradykinin-potentiating factor isolated from scorpion venom (Leiurus quinquestriatus) on some blood indices and lipid profile in irradiated rats - Muhammad M. A. Salman; Ahmed M. Kotb; Mohie A. M. Haridy; Klaus Golka; Seddik Hammad (Molecular and Cellular Biochemistry, 2017)

Spatiotemporal patterns of correlation between atmospheric nitrogen dioxide and aerosols over South Asia - Zia ul-Haq; Salman Tariq; Muhammad Ali (Meteorology and Atmospheric Physics, 2017)

Antimicrobial and antioxidant activities of a new metabolite from Quercus incana - Farah Gul; Khalid Mohammed Khan; Achyut Adhikari; Salman Zafar; Muhammad Akram; Haroon Khan; Muhammad Saeed (Natural Product Research, 2017)

A new glycosidic antioxidant from Ranunculus muricatus L. (Ranunculaceae) exhibited lipoxygenasae and xanthine oxidase inhibition properties - Naila Raziq; Muhammad Saeed; Muhammad Shaiq Ali; Salman Zafar; Muhammad Shahid; Mehreen Lateef (Natural Product Research, 2017)

Cytotoxic cardiac glycosides from the fruit (pods) of Adenium obesum (Forssk.) Roem. & Schult - Salman Khalid Ahmed; Muhammad Ali Versiani; Ambreen Ikram; Samina Abdul Sattar; Shaheen Faizi (Natural Product Research, 2017)

Influence of ameliorating soil acidity with dolomite on the priming of soil C content and CO2 emission - Muhammad Shaaban; Lei Wu; Qi-an Peng; Lukas van Zwieten; Muhammad Afzal Chhajro; Yupeng Wu; Shan Lin; Muhammad Mahmood Ahmed; Muhammad Salman Khalid; Muhammad Abid; Ronggui Hu (Environmental Science and Pollution Research, 2017)

Satellite-sensed tropospheric NO 2 patterns and anomalies over Indus, Ganges, Brahmaputra, and Meghna river basins - Zia ul-Haq; Salman Tariq; Muhammad Ali; Asim Daud Rana; Khalid Mahmood (International Journal of Remote Sensing, 2017)

Use of TALEs and TALEN Technology for Genetic Improvement of Plants - Zulqurnain Khan; Sultan Habibullah Khan; Muhammad Salman Mubarik; Bushra Sadia; Aftab Ahmad (Plant Molecular Biology Reporter, 2017)

Differences in photosynthetic syndromes of four halophytic marsh grasses in Pakistan - Muhammad Moinuddin; Salman Gulzar; Abdul Hameed; Bilquees Gul; M. Ajmal Khan; Gerald E. Edwards (Photosynthesis Research, 2017)

Functional Analysis of VvBG1 During Fruit Development and Ripening of Grape - Haifeng Jia; Chen Wang; Cheng Zhang; Muhammad Salman Haider; Pengcheng Zhao; Zhongjie Liu; Lingfei Shangguan; Tariq Pervaiz; Jinggui Fang (Journal of Plant Growth Regulation, 2016)

Construction Materials from Stainless Steel Slags: Technical Aspects, Environmental Benefits, and Economic Opportunities - Muhammad Salman; Maarten Dubois; Andrea Di Maria; Karel Van Acker; Koenraad Van Balen (Journal of Industrial Ecology, 2016)
Summary State‐of‐the‐art technologies that implement theindustrial ecology concept only make it to the market if environmental gains and economic benefits are significant. Therefore, the article investigates, in an interdisciplinary way, two innovative technologies that valorize stainless steel (SS) slags as block masonry (bricks): carbonation and thermo‐alkali‐activation. The technical, environmental, and economic features of three SS bricks—solid bricks, perforated bricks, and lightweight aerated blocks—are compared to commercially available construction materials. Although the produced bricks meet industrial standards, technical challenges, such as optimization of alkali addition and use of metal molds, should be dealt with before upscaling to industrial production. A cradle‐to‐gate life cycle assessment that aggregates the results of the various impact categories shows that the environmental impact of solid and perforated SS bricks is lower than the impact of conventional clay‐baked bricks owing to the avoidance of additives for slag stabilization and energy consumption for sintering clay. The impact of aerated SS bricks was found to be similar to the commercially available aerated blocks. More specifically, the carbon dioxide uptake from carbonation reduces the overall environmental impact, whereas use of alkalis increases the impact. A strengths weaknesses opportunity threats analysis highlights the economic advantages of SS bricks originating from lower energy requirements, reduced dependence on primary resources, and improved metal recovery from slag. However, in order to apply the innovative technologies at industrial scale, challenges related to processing conditions, feedstock variability, and potential competition from existing brick suppliers have to be overcome.

Emission quantification of refrigerant CFCs, HCFCs and HFCs in megacity Lahore (Pakistan) and contributed ODPs and GWPs - Zia Ul-Haq; Muhammad Ali; Syeda Adila Batool; Salman Tariq; Zarmina Qayyum (Journal of Earth System Science, 2016)

Sulphur dioxide loadings over megacity Lahore (Pakistan) and adjoining region of Indo-Gangetic Basin - Zia ul-Haq; Salman Tariq; Muhammad Ali; Khalid Mahmood; Asim Daud Rana (International Journal of Remote Sensing, 2016)

New dammarane and ursane-type triterpenoids from the flower of Ixora coccinea Linn. - Ambreen Ikram; Muhammad Ali Versiani; Amna Khatoon; Salman Khalid Ahmed; Samina Abdul Sattar; Shaheen Faizi (Natural Product Research, 2016)

Satellite and ground-based remote sensing of aerosols during intense haze event of October 2013 over lahore, Pakistan - Salman Tariq; ul-Haq Zia; Muhammad Ali (Asia-Pacific Journal of Atmospheric Sciences, 2016)

Synthesis and biological activities of 2-aminophenol-based Schiff bases and their structure–activity relationship - Muhammad Aslam; Itrat Anis; Rashad Mehmood; Lubna Iqbal; Samina Iqbal; Inamullah Khan; Muhammad Salman Chishti; Shagufta Perveen (Medicinal Chemistry Research, 2016)

Spectral decomposition application for analyzing the structure and the reservoir potential: a case study of Penobscot, Nova Scotia offshore, Canada - Shazia Asim; Salman Ahmad; Peimin Zhu; Muhammad Tayyab Naseer; Mehwish Butt (Arabian Journal of Geosciences, 2016)

In vitro anti-oxidant potential of new metabolites from Hypericum oblongifolium (Guttiferae) - Naila Raziq; Muhammad Saeed; Muhammad Shaiq Ali; Salman Zafar; Muhammad Imran Ali (Natural Product Research, 2015)

Microwave Assisted Synthesis, Physicochemical, Photophysical, Single Crystal X-ray and DFT Studies of Novel Push–Pull Chromophores - Salman A. Khan; Abdullah M. Asiri; Hadi Mussa Basisi; Muhammad Nadeem Arshad; Kamlesh Sharma (Journal of Fluorescence, 2015)

Biosorption of heavy metals from aqueous solutions using indigenous and modified lignocellulosic materials - Muhammad Salman; Makshoof Athar; Umar Farooq (Reviews in Environmental Science and Bio/Technology, 2015)

Erratum to: Synthesis crystal structure of 2-methoxybenzoylhydrazones and evaluation of their α-glucosidase and urease inhibition potential - Muhammad Taha; Nor Hadiani Ismail; Mohd Syukri Baharudin; Salima Lalani; Sadia Mehboob; Khalid Mohammed Khan; Sammer Yousuf; Salman Siddiqui; Fazal Rahim; M. Iqbal Choudhary (Medicinal Chemistry Research, 2015)

Synthesis crystal structure of 2-methoxybenzoylhydrazones and evaluation of their α-glucosidase and urease inhibition potential - Muhammad Taha; Nor Hadiani Ismail; Mohd Syukri Baharudin; Salima Lalani; Sadia Mehboob; Khalid M. Khan; Sammer yousuf; Salman Siddiqui; Fazal Rahim; M. Iqbal Choudhary (Medicinal Chemistry Research, 2015)

Satellite remote sensing of total ozone column (TOC) over Pakistan and neighbouring regions - Zia Ul-Haq; Salman Tariq; Asim Daud Rana; Muhammad Ali; Khalid Mahmood; Parvez Shahid (International Journal of Remote Sensing, 2015)

Photodegradation of Moxifloxacin in Aqueous and Organic Solvents: A Kinetic Study - Iqbal Ahmad; Raheela Bano; Syed Ghulam Musharraf; Sofia Ahmed; Muhammad Ali Sheraz; Qamar ul Arfeen; Muhammad Salman Bhatti; Zufi Shad (AAPS PharmSciTech, 2014)

Cattle egrets as a biosentinels of persistent organic pollutants exposure - Mudassar Khan; Ashiq Mohammad; Karam Ahad; Athanasios Katsoyiannis; Salman Akbar Malik; Muhammad Abdullaha; Azhar Rashid; Mauro Fasola; Alamdar Hussain; Habib Bokhari; Syed Ali Musstjab Akber Shah Eqani (Environmental Geochemistry and Health, 2014)

Identification of recurrent c.742G>T nonsense mutation in ECM1 in Pakistani families suffering from lipoid proteinosis - Muhammad Nasir; Simeen Ber Rahman; Christian M. K. Sieber; Asif Mir; Amir Latif; Nafees Ahmad; Salman Akbar Malik; Abdul Hameed (Molecular Biology Reports, 2014)

A study of aerosol properties over Lahore (Pakistan) by using AERONET data - Muhammad Ali; Salman Tariq; Khalid Mahmood; Asim Daud; Adila Batool; Zia-ul-Haq (Asia-Pacific Journal of Atmospheric Sciences, 2014)

Tree species as a potential source of bio-herbicides for controlling Parthenium hysterophorus L. - Muhammad Ehsan Safdar; Asif Tanveer; Abdul Khaliq; Muhammad Shahbaz Naeem; Salman Ahmad (Natural Product Research, 2013)

Genetic diversity in human malarial parasites of Khyber Agency Pakistan - Lubna Khatoon; Muhammad Jan; Inam Khan; Farhat Ullah; Salman Malik (Acta Parasitologica, 2013)
Malaria is wide spread in poor world and its burden has been assessed by the enumeration of malarial parasites in blood of patients. This study was designed to find a relationship between social structure, and spread of malaria in Khyber agency. The average parasite density was 2050 parasite/μl in Khyber Agency. Due to economic and social setup most of the people have habit of sleeping in open air thus playing role in high malaria prevalence and Plasmodium vivax remains the prevalent species. Genetic study performed on 110 Blood samples showed less genetic diversity for both Plasmodium vivax and Plasmodium falciparum. Eight alleles were distinguished both for Pvmsp 3α and Pvmsp 3β in total of 20 and 39 amplified samples of P. vivax respectively. Out of 17 samples amplified for P. falciparum 11 showed genotype K1 and 10 for MAD at Pfmsp-1 while 14 alleles were identified for 3D7/1C and two for FC27 of corresponding families of Pfmsp-2 gene. This shows that Plasmodium parasites are not genetically diverse in Khyber agency.

Transfer of radioactivity from soil to vegetation in Rechna Doab, Pakistan - Abdul Jabbar; Muhammad Tufail; Waheed Arshed; Arshed Salem Bhatti; Syed Salman Ahmad; Perveen Akhter; Muhammad Dilband (Isotopes in Environmental and Health Studies, 2010)

Expression of rol genes in transgenic soybean (Glycine max L.) leads to changes in plant phenotype, leaf morphology, and flowering time - Muhammad Zia; Bushra Mirza; Salman Akbar Malik; Muhammad Fayyaz Chaudhary (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Measurement of soil radioactivity levels and radiation hazard assessment in southern Rechna interfluvial region, Pakistan - Abdul Jabbar; Waheed Arshed; Arshad Saleem Bhatti; Syed Salman Ahmad; Perveen Akhter; Saeed -Ur -Rehman; Muhammad Iftikhar Anjum (Environmental Monitoring and Assessment, 2010)

Novel mutations in G protein-coupled receptor gene (P2RY5) in families with autosomal recessive hypotrichosis (LAH3) - Zahid Azeem; Musharraf Jelani; Gul Naz; Muhammad Tariq; Naveed Wasif; Syed Kamran-ul-Hassan Naqvi; Muhammad Ayub; Masoom Yasinzai; Muhammad Amin-ud-din; Abdul Wali; Ghazanfar Ali; Muhammad Salman Chishti; et al. (Human Genetics, 2008)

A syndromic form of autosomal recessive congenital microcephaly (Jawad syndrome) maps to chromosome 18p11.22–q11.2 - Muhammad Jawad Hassan; Muhammad Salman Chishti; Syed Muhammad Jamal; Muhammad Tariq; Wasim Ahmad (Human Genetics, 2008)

A mutation in the lipase H (LIPH) gene underlie autosomal recessive hypotrichosis - Ghazanfar Ali; Muhammad Salman Chishti; Syed Irfan Raza; Peter John; Wasim Ahmad (Human Genetics, 2007)